Marine migration influences mercury accumulation in anadromous Arctic char ( Salvelinus alpinus ) - Isabel R. Hilgendag; Michael Power; Mehdi M. Aqdam; Christopher W. Lewis; Zoya Martin; Ashley D. Ehrman; Heidi K. Swanson (Journal of Fish Biology, 2026)
Mercury (Hg) is a globally distributed toxic metal present in northern natural environments that biomagnifies in food webs and bioaccumulates in apex predator fish, such as Arctic char ( Salvelinus alpinus )—an iteroparous species with a circumpolar distribution. Arctic char exhibit a variety of life history types, with the migrating, anadromous life‐history type supporting many subsistence and small‐scale commercial fisheries in the Arctic and sub‐Arctic. Despite anadromous Arctic char having generally lower Hg concentrations than non‐anadromous conspecifics, the mechanisms that contribute to significant inter‐individual differences within this life‐history group have not been well investigated. A total of 119 anadromous Arctic char were captured from inner Frobisher Bay on Baffin Island near Iqaluit, Nunavut, in 2018 and 2019, to investigate causes of inter‐individual differences in Hg concentrations in the anadromous life‐history type of Arctic char. As hypothesized, Hg concentrations significantly decreased with increasing marine prey reliance; marine prey reliance—quantified using δ 34 S ratios—explained 93% of the variability in Hg. Arctic char that relied more on marine (vs freshwater) prey had lower Hg concentrations. Delta 34 S ratios and average somatic growth rate (size‐at‐age) were the best predictors of Hg concentrations among the set of biological variables assessed, and both were negatively related to Hg concentrations in common age groups (i.e., ages 9–13). For samples that had migration data available, Hg concentration increased with age‐at‐first migration ( R 2 = 0.32) and decreased with number of marine migrations ( R 2 = 0.57), suggesting that plasticity in life history tactics affects Hg concentrations in anadromous Arctic char. Overall, results indicate that differences in habitat use and feeding environment (i.e., freshwater vs. marine) play a significant role in determining Hg bioaccumulation in anadromous Arctic char.

A battleground of climate change: Summer air temperatures in social housing - Sebastian Pfautsch; Agnieszka Wujeska-Klause; Judi R. Walters; Abby Mellick Lopes; Louise Crabtree-Hayes; Emma Power; Bhavya Chitranshi; Helen Armstrong; Katherine Gibson; Cameron Tonkinwise; Stephen Healy (Urban Climate, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Effects of electrical cutaneous stimulation of the foot sole on voluntary plantarflexion rate of torque development after fatigue in males - Laura C. Marrelli; Tushar Sharma; Ashley V. Vanderhaeghe; Geoffrey A. Power; Leah R. Bent (European Journal of Applied Physiology, 2026)

Multi-millennial reconstruction of fire return intervals from a fynbos – Afrotemperate forest ecotone in the Cape Floristic Region, South Africa: Paleoecological implications for present-day management - Stella G. Mosher; Mitchell J. Power; Lynne J. Quick; Brian M. Chase; Torsten Haberzettl; Thomas Kasper; Simon C. Brewer; David R. Braun; J. Tyler Faith (Global and Planetary Change, 2026)

Characterization of a precipitate sludge from a sulfuric acid plant - Simon P. Michaux; Alan R. Butcher; Duncan Pirrie; Jarno Mäkinen; Mari Lundström; Petri Latostenmaa; Jesal Hirani; Nikolaos Apeiranthitis; Tero Korhonen; Matthew R. Power (Minerals Engineering, 2026)

Regional ecosystem responses to environmental drivers in cold‐water lakes evaluated using stable isotopes of salmonid fishes - Matthew R. D. Cobain; Per‐Arne Amundsen; Åge Brabrand; Pär Byström; Jan G. Davidsen; Karl Ø. Gjelland; Jennifer E. Hansen; Ingeborg P. Helland; Trygve Hesthagen; Stein I. Johnsen; Roger I. Jones; Kimmo K. Kahilainen; et al. (Limnology and Oceanography, 2026)
Diverse environmental drivers influence food web energy and nutrient flows, a key ecosystem function, yet their relative importance remains poorly known. We compiled thousands of bulk stable isotope measurements (carbon and nitrogen) of brown trout ( Salmo trutta , n = 2854) and Arctic charr ( Salvelinus alpinus , n = 3062) from 120 cold‐water lakes across northern Europe, spanning 0.02 to 1090 km 2 in size, to quantify the relative importance of nine potential drivers of energy and nutrient flows. Fish community type and individual body size matched the well‐described ecologies of the two species: charr shifted from littoral to pelagic sources with interspecific competition, and trout opportunistically increased their trophic position with piscivorous prey availability and increasing body size. The anthropogenic impacts of water‐level regulation and catchment modification were mirrored in the two species, resulting in decreased δ 13 C values, implying increased relative pelagic production in regulated lakes, and increased δ 15 N values, possibly due to increasing cross‐boundary nutrient flows. Lake size and climatic drivers (summer precipitation and winter temperature) elicited strong species‐specific changes in isotope values, suggesting that predator‐driven ecological responses can dominate over ecosystem‐wide changes in energy and nutrient flows within lake food webs. No isotopic trends were observed with catchment productivity or shoreline complexity at the regional scale, contrasting with insights from local scale studies. This spatial mismatch suggests that environmental drivers of ecosystem processes playing out at the regional scale cannot necessarily be extrapolated from localized studies, despite correlated random lake effects capturing unexplained local baseline shifts in isotopes.

Global Review of Greater Amberjack ( Seriola dumerili ) Life History - Mischa K. Schultz; Michael A. Dance; Sean Powers; Stephen R. Midway (Reviews in Fisheries Science & Aquaculture, 2025)

Evaluating climatic and anthropogenic drivers of fire activity over four millennia at Eilandvlei, southern Cape coast, South Africa - Stella G. Mosher; Mitchell J. Power; Brian M. Chase; Lynne J. Quick; Torsten Haberzettl; Thomas Kasper; David R. Braun; J. Tyler Faith (Quaternary Science Reviews, 2025)

Improving Access to Care: Leveraging Virtual Weight Management Education Groups for New Patients in Rural and Suburban Communities - J. Powers; J. Fisher; S. Coolbaugh; A. Zammit; R. Dumont; S. Cortese (Journal of the Academy of Nutrition and Dietetics, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Equine microbiome shifts with dietary mannan-rich fraction inclusion - M. Brummer-Holder; R. Power (Journal of Equine Veterinary Science, 2025)

Optimizing the management of quarry fines for on-site carbon removal: Implications of grain size and mineralogy on CO2 mineralization - Amanda R. Stubbs; Faisal W.K. Khudhur; Ian M. Power; Linzi McDade; Mark Friel; Iain Neill; John MacDonald (International Journal of Greenhouse Gas Control, 2025)

Supplemental Feeding as a Driver of Population Expansion and Morphological Change in Anna's Hummingbirds - Nicolas M. Alexandre; Faye G. Romero; Simon G. English; Eliza Grames; Felipe Garzón‐Agudelo; Kevin Epperly; Timothy Barnes; Donald R. Powers; Audrey E. Smith; Zoë Migicovsky; Laura Stein; Saron Akalu; et al. (Global Change Biology, 2025)
Bird beaks are highly adaptable, with the potential to undergo rapid morphological shifts in response to environmental change such as climatic variation or food availability. Anna's Hummingbirds ( Calypte anna ) have undergone dramatic population range expansions over the last 160 years into novel climatic regimes, where supplemental feeders and introduced plant species are frequented. We used museum specimens to measure and characterize the shape of Anna's Hummingbird bills, hypothesizing that the introduction of novel food sources and the colonization of colder climates were associated with distinct dimensions of beak morphology. We estimated feeder and Eucalyptus availability using data from archived newspaper databases and found that these two abundances are linked to population increases in Anna's Hummingbirds, while feeders were associated with changes to beak morphology. We found that bill size and shape changed with feeder use, exhibiting a more tapered and longer bill and a distinct maxillary constriction. In males, dorsal bill shape increased in pointedness, which may have provided an advantage with increased agonistic encounters at feeders. In contrast, bill size decreased in association with lower temperatures at higher latitudes. Our data document rapid morphological changes in the Anna's Hummingbird's bill induced by human‐caused environmental changes over the last century.

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

The nature of microbial diversity and assembly in the Nebraska Sandhills depends on organismal identity and habitat type - Kaitlin Gattoni; Eli M. S. Gendron; J. Parr McQueen; Kirsten Powers; Thomas O. Powers; Mary J. Harner; Jessica R. Corman; Dorota L. Porazinska (Community Ecology, 2025)

Chemical Composition of Secretions from Facial Glands of Captive Hoary Bat (Lasiurus cinereus) in Virginia - Kristina R. Stefaniak; Lark Kellogg; Matthew T. Close; Karen E. Powers (Journal of Chemical Ecology, 2025)
Our study represents the first known report of hoary bat ( Lasiurus cinereus ) facial gland histology and chemical characterization of facial gland secretions. While in captivity from October 2023 to February 2024, facial secretions of a male hoary bat were observed and collected. Gas chromatography-mass spectrometry (GC-MS) analysis of a methanol extraction of November 2023 samples identified 23 compounds after comparing retention times, mass spectra, and Kovats retention index. These compounds consisted of alkanes, alcohols, ketones, terpenoids, monoacylglycerols, and androgens. Of interest was the identification of five androstane derivatives, testosterone metabolites, that have not been seen previously in mammal secretions and indicate possible mating readiness. The chemical analyses from November swabs and histological examination of facial skin in February suggest that this male was actively secreting mate-signaling compounds throughout late fall and winter months. Anecdotal mating records on wintering grounds combined with this bat’s warm captive environment likely allowed for this extended mating readiness for his many months at the wildlife center.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Remote sensing for species distribution models: An illustration from a sentinel taxon of the world's driest ecosystem - Khum B. Thapa‐Magar; Eric R. Sokol; Michael N. Gooseff; Mark R. Salvatore; John E. Barrett; Joseph S. Levy; Paul Knightly; Sarah N. Power (Ecology, 2025)
In situ observed data are commonly used as species occurrence response variables in species distribution models. However, the use of remotely observed data from high‐resolution multispectral remote‐sensing images as a source of presence/absence data for species distribution models remains under‐developed. Here, we describe an ensemble species distribution model of black microbial mats ( Nostoc spp.) using presence/absence points derived from the unmixing of 4‐m resolution WorldView‐2 and WorldView‐3 images in the Lake Fryxell basin region of Taylor Valley, Antarctica. Environmental and topographical characteristics such as soil moisture, snow, elevation, slope, and aspect were used as predictor variables in our models. We demonstrate that we can build and run ensemble species distribution models using both dependent and independent variables derived from remote‐sensing data to generate spatially explicit habitat suitability maps. Snow and soil moisture were found to be the most important variables accounting for about 80% of the variation in the distribution of black mats throughout the Fryxell basin. This study highlights the potential contribution of high‐resolution remote‐sensing to species distribution modeling and informs new studies incorporating remotely derived species occurrences in species distribution models, especially in remote areas where access to in situ data is often limited.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Weathering and cementation of historic kimberlite residues from South Africa: Implications for residue stabilization and CO2 sequestration - Justin A. Lockhart; Ian M. Power; Carlos Paulo; Amanda R. Stubbs; Nina Zeyen; Sasha Wilson; Matthew Steele-MacInnis; Robert Caldwell; Chris Gunning (Science of The Total Environment, 2024)

Effects of a Fruit and Vegetable Supplement on the Skin Carotenoid Scores in Healthy Adults: A Pilot Study - R. Brooks; C. Washburn; M. Powers; J. Mayo; A. Landry (Journal of the Academy of Nutrition and Dietetics, 2024)

From field station to forecast: managing data at the Alaska Volcano Observatory - Michelle L. Coombs; Cheryl E. Cameron; Hannah R. Dietterich; Eleanor S. Boyce; Aaron G. Wech; Ronni Grapenthin; Kristi L. Wallace; Tom Parker; Taryn Lopez; Scott Crass; David Fee; Matthew M. Haney; et al. (Bulletin of Volcanology, 2024)

Potential landscape connectivity for invasive wild pigs (Sus scrofa) across the northern prairies of North America - Corey J. Kramer; Melanie R. Boudreau; Ryan Powers; Kurt C. VerCauteren; Ryan S. Miller; Ryan K. Brook (Biological Invasions, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Impact of turbidity on the gill morphology and hypoxia tolerance of eastern sand darter ( Ammocrypta pellucida ) - Britney L. Firth; Paul M. Craig; D. Andrew R. Drake; Michael Power (Journal of Fish Biology, 2024)
Anthropogenic stressors such as agriculture and urbanization can increase river turbidity, which can negatively impact fish gill morphology and growth due to reduced oxygen in the benthic environment. We assessed the gill morphology, field metabolic rate (FMR), and two hypoxia tolerance metrics (oxygen partial pressure at loss of equilibrium, PO 2 at LOE, and critical oxygen tension, P crit ) of eastern sand darter ( Ammocrypta pellucida ), a small benthic fish listed as threatened under the Species at Risk Act in Canada, from rivers in southern Ontario. Field trials were conducted streamside in the Grand River (August 2019; mean NTU 8) and in the comparatively more turbid Thames River (August 2020; mean NTU 94) to test the effect of turbidity on each physiological endpoint. Gills were collected from incidental mortalities and museum specimens, and were assessed using hematoxylin and eosin and immunofluorescent staining. The between‐river comparison indicated that turbidity significantly increased interlamellar space and filament width but had no significant influence on other gill morphometrics or FMR. Turbidity significantly increased PO 2 at LOE (i.e., fish had a lower hypoxia tolerance) but did not significantly impact P crit . Therefore, although turbidity influences hypoxia tolerance through LOE, turbidity levels were not sufficiently high in the study rivers to contribute to measurable changes in gill morphology or metabolism in the wild. Determining whether changes in gill morphology or metabolism occur under higherturbidity levels would help resolve the ecological importance of turbidity on species physiology in urban and agricultural ecosystems.

Local environment shapes milk microbiomes while evolutionary history constrains milk macronutrients in captive cercopithecine primates - Sally L. Bornbusch; Hannah E. Shinnerl; Lindsey Gentry; Mia M. Keady; Virginia Glick; Carly R. Muletz‐Wolz; Michael L. Power (Environmental Microbiology, 2024)
Milk is a complex biochemical fluid that includes macronutrients and microbiota, which, together, are known to facilitate infant growth, mediate the colonization of infant microbiomes, and promote immune development. Examining factors that shape milk microbiomes and milk‐nutrient interplay across host taxa is critical to resolving the evolution of the milk environment. Using a comparative approach across four cercopithecine primate species housed at three facilities under similar management conditions, we test for the respective influences of the local environment (housing facility) and host species on milk (a) macronutrients (fat, sugar, and protein), (b) microbiomes (16S rRNA), and (c) predicted microbial functions. We found that milk macronutrients were structured according to host species, while milk microbiomes and predicted function were strongly shaped by the local environment and, to a lesser extent, host species. The milk microbiomes of rhesus macaques ( Macaca mulatta ) at two different facilities more closely resembled those of heterospecific facility‐mates compared to conspecifics at a different facility. We found similar, facility‐driven patterns of microbial functions linked to physiology and immune modulation, suggesting that milk microbiomes may influence infant health and development. These results provide novel insight into the complexity of milk and its potential impact on infants across species and environments.

Experimental and computational fluid-structure interaction analysis and optimization of Deep-V planing-hull grillage panels subject to slamming loads – Part II: Irregular waves - Evan J. Lee; Matteo Diez; Emily L. Harrison; Minyee J. Jiang; Lawrence A. Snyder; Ann Marie R. Powers; Raymond J. Bay; Andrea Serani; Maria L. Nadal; Eric R. Kubina; Frederick Stern (Ocean Engineering, 2024)

Dietary Habits of Hardhead (Ariopsis felis) and Gafftopsail (Bagre marinus) Catfish Revealed through DNA Barcoding of Stomach Contents - Ana R. Osowski; Matthew B. Jargowsky; Pearce T. Cooper; Sean P. Powers; J. Marcus Drymon (Fishes, 2023)
A better understanding of trophic interactions between hardhead catfish (Ariopsis felis) and gafftopsail catfish (Bagre marinus) is crucial for developing multi-species management strategies for the northern Gulf of Mexico (GOM). These two species are often aggregated in food web models; however, limited data are available to substantiate this approach. Therefore, the present study aimed to describe the dietary habits of hardhead catfish and gafftopsail catfish using analysis of stomach contents aided by DNA barcoding. Hardhead (n = 693) and gafftopsail (n = 655) catfish were sampled in the northern GOM from 2015–2019 using both fisheries-dependent and -independent techniques. The average percent number (%N), average percent mass (%M), prey specific number (%PN), prey specific mass (%PM), and prey-specific index of relative importance (%PSIRI) were computed to quantify prey species. The stomach content analysis identified distinct differences in diet between hardhead and gafftopsail catfish. Crustaceans were the most important prey for hardhead catfish, while gafftopsail catfish showed a significantly broader dietary breadth and were primarily piscivorous. Multivariate analyses indicated that the location of capture explained the greatest amount of diet variability for both species. These findings address fundamental knowledge gaps regarding the dietary habits of hardhead and gafftopsail catfish in northern GOM ecosystems.

Impact of wet-dry cycles on enhanced rock weathering of brucite, wollastonite, serpentinite and kimberlite: Implications for carbon verification - Amanda R. Stubbs; Ian M. Power; Carlos Paulo; Baolin Wang; Nina Zeyen; Sasha Wilson; Evelyn Mervine; Chris Gunning (Chemical Geology, 2023)

Evolving etiologies, comorbidities, survival, and costs of care in adult encephalitis - J. A. Bakal; R. Rivera; C. Charlton; S. Plitt; C. Power (Journal of NeuroVirology, 2023)

An improved method for computing tidal datums - Karen Palmer; Christopher S. Watson; John R. Hunter; Ben S. Hague; Hannah E. Power (Coastal Engineering, 2023)

Evaluating the fidelity of enamel isotopic data and environmental variation in paleoecological studies: A case study in wild, known-aged, modern white-tailed deer (Odocoileus virginianus) - Taylor Malasek; Erin Barding; Michael J. Bender; Alexandra Bonham; Alfred J. Mead; Zachary Pilgrim; Patrick Powers; Jessica R. Patterson; David B. Patterson (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The Western Lake Erie culture collection: A promising resource for evaluating the physiological and genetic diversity of Microcystis and its associated microbiome - Colleen E. Yancey; E. Anders Kiledal; Subba Rao Chaganti; Vincent J. Denef; Reagan M. Errera; Jacob T. Evans; Lauren N. Hart; Dragan Isailovic; William S. James; Jenan J. Kharbush; Jeffrey A. Kimbrel; Wei Li; et al. (Harmful Algae, 2023)

Deconstructing heterogeneity of replicative senescence in human mesenchymal stem cells at single cell resolution - Atefeh Taherian Fard; Hannah C. Leeson; Julio Aguado; Giovanni Pietrogrande; Dominique Power; Cecilia Gómez-Inclán; Huiwen Zheng; Christopher B. Nelson; Farhad Soheilmoghaddam; Nick Glass; Malindrie Dharmaratne; Ebony R. Watson; et al. (GeroScience, 2023)
Following prolonged cell division, mesenchymal stem cells enter replicative senescence, a state of permanent cell cycle arrest that constrains the use of this cell type in regenerative medicine applications and that in vivo substantially contributes to organismal ageing. Multiple cellular processes such as telomere dysfunction, DNA damage and oncogene activation are implicated in promoting replicative senescence, but whether mesenchymal stem cells enter different pre-senescent and senescent states has remained unclear. To address this knowledge gap, we subjected serially passaged human ESC-derived mesenchymal stem cells (esMSCs) to single cell profiling and single cell RNA-sequencing during their progressive entry into replicative senescence. We found that esMSC transitioned through newly identified pre-senescent cell states before entering into three different senescent cell states. By deconstructing this heterogeneity and temporally ordering these pre-senescent and senescent esMSC subpopulations into developmental trajectories, we identified markers and predicted drivers of these cell states. Regulatory networks that capture connections between genes at each timepoint demonstrated a loss of connectivity, and specific genes altered their gene expression distributions as cells entered senescence. Collectively, this data reconciles previous observations that identified different senescence programs within an individual cell type and should enable the design of novel senotherapeutic regimes that can overcome in vitro MSC expansion constraints or that can perhaps slow organismal ageing.

Stable isotopes and foraging behaviors support the role of antipredator benefits in driving the association between two marine fishes - Christopher R. Haak; Michael Power; Alexander D. M. Wilson; Andy J. Danylchuk (Oecologia, 2023)

Drivers of the microbial metabolic quotient across global grasslands - A. C. Risch; S. Zimmermann; M. Schütz; E. T. Borer; A. A. D. Broadbent; M. C. Caldeira; K. F. Davies; N. Eisenhauer; A. Eskelinen; P. A. Fay; F. Hagedorn; J. M. H. Knops; et al. (Global Ecology and Biogeography, 2023)
Aim The microbial metabolic quotient (MMQ; mg CO 2 ‐C/mg MBC/h), defined as the amount of microbial CO 2 respired (MR; mg CO 2 ‐C/kg soil/h) per unit of microbial biomass C (MBC; mg C/kg soil), is a key parameter for understanding the microbial regulation of the carbon (C) cycle, including soil C sequestration. Here, we experimentally tested hypotheses about the individual and interactive effects of multiple nutrient addition (nitrogen + phosphorus + potassium + micronutrients) and herbivore exclusion on MR, MBC and MMQ across 23 sites (five continents). Our sites encompassed a wide range of edaphoclimatic conditions; thus, we assessed which edaphoclimatic variables affected MMQ the most and how they interacted with our treatments. Location Australia, Asia, Europe, North/South America. Time period 2015–2016. Major taxa Soil microbes. Methods Soils were collected from plots with established experimental treatments. MR was assessed in a 5‐week laboratory incubation without glucose addition, MBC via substrate‐induced respiration. MMQ was calculated as MR/MBC and corrected for soil temperatures (MMQsoil). Using linear mixed effects models (LMMs) and structural equation models (SEMs), we analysed how edaphoclimatic characteristics and treatments interactively affected MMQsoil. Results MMQsoil was higher in locations with higher mean annual temperature, lower water holding capacity and lower soil organic C concentration, but did not respond to our treatments across sites as neither MR nor MBC changed. We attributed this relative homeostasis to our treatments to the modulating influence of edaphoclimatic variables. For example, herbivore exclusion, regardless of fertilization, led to greater MMQsoil only at sites with lower soil organic C ( Main conclusions Our results pinpoint the main variables related to MMQsoil across grasslands and emphasize the importance of the local edaphoclimatic conditions in controlling the response of the C cycle to anthropogenic stressors. By testing hypotheses about MMQsoil across global edaphoclimatic gradients, this work also helps to align the conflicting results of prior studies.

121 Impact of environmental conditions and dragging schedules on changes in moisture content in equine arena footing - S. McGill; M. Hayes; K. Power; M. Peterson; R. Coleman (Journal of Equine Veterinary Science, 2023)

120 Determining moisture content in equine arena footing on-farm - S. McGill; M. Hayes; K. Power; M. Peterson; R. Coleman (Journal of Equine Veterinary Science, 2023)

Influence of topical capsaicin cream on thermoregulation and perception during acute exercise in the heat - Alejandro M. Rosales; Marie Powers; Matthias J. Walters; Mark L. McGlynn; Christopher W. Collins; Dustin R. Slivka (Journal of Thermal Biology, 2023)

The impacts of a global pandemic on the efficacy and stability of contemporary wildlife conservation: South Africa as a case study - David A. Ehlers Smith; Yvette C. Ehlers Smith; Harriet T. Davies-Mostert; Lindy J. Thompson; Daniel M. Parker; Deon de Villiers; Dean Ricketts; Brent Coverdale; Peter J. Roberts; Christopher Kelly; Duncan N. Macfadyen; Nomthandazo S. Manqele; et al. (Ambio, 2023)
Conservationists speculated on potential benefits to wildlife of lockdown restrictions because of the COVID-19 pandemic but voiced concern that restrictions impeded nature conservation. We assessed the effects of lockdown restrictions on biodiversity conservation in South Africa, a biodiverse country with economic inequality and reliance on wildlife resources. We solicited expert opinion using the IUCN’s Threats Classification Scheme to structure a questionnaire and illustrated responses with individual case studies from government parastatal and non-governmental conservation organisations. The most highly reported threats were biological resource use, residential/commercial developments, invasive species, and human intrusions. The trends reported by 90 survey respondents were supported by case studies using environmental compliance data from parastatal conservation organisations. Lack of tourism revenue and funding were cited as hindrances to conservation. Mechanisms to prevent environmental degradation in the face of global emergencies must be implemented and ‘ring-fenced’ to ensure conservation is not a casualty during future global crises.

Free-living Allen’s hummingbirds (Selasphorus sasin) rarely use torpor while nesting - Erich R. Eberts; Glenn J. Tattersall; Peter J. Auger; Maria Curley; Melissa I. Morado; Eric G. Strauss; Donald R. Powers; Noemi C. Soveral; Bret W. Tobalske; Anusha Shankar (Journal of Thermal Biology, 2023)

Ecological stoichiometry and fungal community turnover reveal variation among mycorrhizal partners in their responses to warming and drought - Haiyang Zhang; Amber C. Churchill; Ian C. Anderson; Chioma Igwenagu; Sally A. Power; Jonathan M. Plett; Catriona A. Macdonald; Elise Pendall; Yolima Carrillo; Jeff R. Powell (Molecular Ecology, 2023)
Symbiotic fungi mediate important energy and nutrient transfers in terrestrial ecosystems. Environmental change can lead to shifts in communities of symbiotic fungi, but the consequences of these shifts for nutrient dynamics among symbiotic partners are poorly understood. Here, we assessed variation in carbon (C), nitrogen (N) and phosphorus (P) in tissues of arbuscular mycorrhizal (AM) fungi and a host plant ( Medicago sativa ) in response to experimental warming and drought. We linked compositional shifts in AM fungal communities in roots and soil to variation in hyphal chemistry by using high‐throughput DNA sequencing and joint species distribution modelling. Compared to plants, AM hyphae was 43% lower in (C) and 24% lower in (N) but more than nine times higher in (P), with significantly lower C:N, C:P and N:P ratios. Warming and drought resulted in increases in (P) and reduced C:P and N:P ratios in all tissues, indicating fungal P accumulation was exacerbated by climate‐associated stress. Warming and drought modified the composition of AM fungal communities, and many of the AM fungal genera that were linked to shifts in mycelial chemistry were also negatively impacted by climate variation. Our study offers a unified framework to link climate change, fungal community composition, and community‐level functional traits. Thus, our study provides insight into how environmental change can alter ecosystem functions via the promotion or reduction of fungal taxa with different stoichiometric characteristics and responses.

Two canonically aerobic foraminifera express distinct peroxisomal and mitochondrial metabolisms - Christopher Powers; Fatma Gomaa; Elizabeth B. Billings; Daniel R. Utter; David J. Beaudoin; Virginia P. Edgcomb; Colleen M. Hansel; Scott D. Wankel; Helena L. Filipsson; Ying Zhang; Joan M. Bernhard (Frontiers in Marine Science, 2022)
Certain benthic foraminifera thrive in marine sediments with low or undetectable oxygen. Potential survival avenues used by these supposedly aerobic protists include fermentation and anaerobic respiration, although details on their adaptive mechanisms remain elusive. To better understand the metabolic versatility of foraminifera, we studied two benthic species that thrive in oxygen-depleted marine sediments. Here we detail, via transcriptomics and metatranscriptomics, differential gene expression of Nonionella stella and Bolivina argentea , collected from Santa Barbara Basin, California, USA, in response to varied oxygenation and chemical amendments. Organelle-specific metabolic reconstructions revealed these two species utilize adaptable mitochondrial and peroxisomal metabolism. N. stella , most abundant in anoxia and characterized by lack of food vacuoles and abundance of intracellular lipid droplets, was predicted to couple the putative peroxisomal beta-oxidation and glyoxylate cycle with a versatile electron transport system and a partial TCA cycle. In contrast, B. argentea , most abundant in hypoxia and contains food vacuoles, was predicted to utilize the putative peroxisomal gluconeogenesis and a full TCA cycle but lacks the expression of key beta-oxidation and glyoxylate cycle genes. These metabolic adaptations likely confer ecological success while encountering deoxygenation and expand our understanding of metabolic modifications and interactions between mitochondria and peroxisomes in protists.

Hyperspectral imaging predicts yield and nitrogen content in grass–legume polycultures - K. R. Ball; H. Liu; C. Brien; B. Berger; S. A. Power; E. Pendall (Precision Agriculture, 2022)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Round Goby (Neogobius melanostomus) impacts on benthic fish communities in two tributaries of the Great Lakes - Keith McAllister; D. Andrew R. Drake; Michael Power (Biological Invasions, 2022)
Numerous fish species in the Laurentian Great Lakes have been negatively impacted by the establishment of the invasive Round Goby ( Neogobius melanostomus ). However, limited understanding exists as to how Round Goby has impacted small-bodied native benthic fishes after its secondary invasion into tributaries of the Laurentian Great Lakes. To investigate Round Goby impacts on darter species (family Percidae) in tributary ecosystems, catch per unit area (CPUA) of native and non-native fishes from two riverine ecosystems in Southwestern Ontario (Ausable River, Big Otter Creek) were analyzed. Spatial analyses indicated Round Goby CPUA was highest proximate to the Great Lakes, with a sharp decline in CPUA at sites upstream from each lake (Round Goby CPUA approached zero after 18 and 14 km in the Ausable River and Big Otter Creek, respectively). There was some evidence of a negative relationship between the CPUA of Round Goby and several darter species along the tributary gradients, with moderately negative co-occurrence between Round Goby and Rainbow Darter in the Ausable River and Johnny Darter and Percidae species overall in Big Otter Creek. However, overwhelming evidence of negative associations between Round Goby and all darter species was not found. The negative relationship between the CPUA of Round Goby and some darter species was observed over similar time periods since establishment but greater spatial scales than in previous studies, and therefore has important implications for understanding the ecological impacts of Round Goby in tributary ecosystems.

Summer ecosystem structure in mountain lakes linked to interannual variability of lake ice, snowpack, and landscape attributes - Stephen M. Powers; Steven C. Fradkin; William Baccus; Carmen Archambault; John R. Boetsch; Matthew R. Brousil; Rebecca Lofgren; Ashley Rawhouser; Stephanie E. Hampton (Limnology and Oceanography, 2022)
Mountain lakes experience interannual variability in spring snowpack and ice cover that can lead to differences in physical, chemical, and biological properties in the succeeding summer. Lake studies that capture extreme years of snow and ice would be useful to understand and anticipate effects of climate change, but such data are rare for remote mountain lakes. Monitoring of lakes in Olympic, North Cascades, and Mount Rainier National Parks from 2007 to 2018 allowed us to examine limnological differences along interannual and elevation‐driven climate gradients that included unusually high (2011–2012) and 100‐yr record low (2015) snowpack years. Years with lower spring snowpack had earlier ice‐out. Across lakes, our analysis suggested an average of 0.075°C lake warming per day of lost ice duration (0.525°C per week), giving rise to other ecosystem changes linked to temperature such as lower dissolved oxygen, higher total dissolved N, higher chlorophyll, and higher abundance of cladoceran zooplankton. Conversely, in years with higher snowpack and a shorter ice‐free season, lakes were colder and clearer (1 m deeper Secchi depth for every 1 m May snow water equivalent), with more dilute ions as well as lower algal biomass and zooplankton abundance. These results add to evidence that changes in snowpack or ice‐out dates alter mountain lake ecology through multiple processes associated with hydrology, terrestrial‐aquatic connection, water temperature, productivity, ion composition, and plankton communities.

Strategies to acquire and use phosphorus in phosphorus-impoverished and fire-prone environments - Hans Lambers; Patrícia de Britto Costa; Gregory R. Cawthray; Matthew D. Denton; Patrick M. Finnegan; Patrick E. Hayes; Rafael S. Oliveira; Simon C. Power; Kosala Ranathunge; Qi Shen; Xiao Wang; Hongtao Zhong (Plant and Soil, 2022)
Background Unveiling the diversity of plant strategies to acquire and use phosphorus (P) is crucial to understand factors promoting their coexistence in hyperdiverse P-impoverished communities within fire-prone landscapes such as in cerrado (South America), fynbos (South Africa) and kwongan (Australia). Scope We explore the diversity of P-acquisition strategies, highlighting one that has received little attention: acquisition of P following fires that temporarily enrich soil with P. This strategy is expressed by fire ephemerals as well as fast-resprouting perennial shrubs. A plant’s leaf manganese concentration ([Mn]) provides significant clues on P-acquisition strategies. High leaf [Mn] indicates carboxylate-releasing P-acquisition strategies, but other exudates may play the same role as carboxylates in P acquisition. Intermediate leaf [Mn] suggests facilitation of P acquisition by P-mobilising neighbours, through release of carboxylates or functionally similar compounds. Very low leaf [Mn] indicates that carboxylates play no immediate role in P acquisition. Release of phosphatases also represents a P-mining strategy, mobilising organic P. Some species may express multiple strategies, depending on time since germination or since fire, or on position in the landscape. In severely P-impoverished landscapes, photosynthetic P-use efficiency converges among species. Efficient species exhibit rapid rates of photosynthesis at low leaf P concentrations. A high P-remobilisation efficiency from senescing organs is another way to use P efficiently, as is extended longevity of plant organs. Conclusions Many P-acquisition strategies coexist in P-impoverished landscapes, but P-use strategies tend to converge. Common strategies of which we know little are those expressed by ephemeral or perennial species that are the first to respond after a fire. We surmise that carboxylate-releasing P-mobilising strategies are far more widespread than envisaged so far, and likely expressed by species that accumulate metals, exemplified by Mn, metalloids, such as selenium, fluorine, in the form of fluoroacetate, or silicon. Some carboxylate-releasing strategies are likely important to consider when restoring sites in biodiverse regions as well as in cropping systems on P-impoverished or strongly P-sorbing soils, because some species may only be able to establish themselves next to neighbours that mobilise P.

SGLT2 inhibition attenuates arterial dysfunction and decreases vascular F-actin content and expression of proteins associated with oxidative stress in aged mice - Rogerio N. Soares; Francisco I. Ramirez-Perez; Francisco J. Cabral-Amador; Mariana Morales-Quinones; Christopher A. Foote; Thaysa Ghiarone; Neekun Sharma; Gavin Power; James A. Smith; R. Scott Rector; Luis A. Martinez-Lemus; Jaume Padilla; et al. (GeroScience, 2022)
Aging of the vasculature is characterized by endothelial dysfunction and arterial stiffening, two key events in the pathogenesis of cardiovascular disease (CVD). Treatment with sodium glucose transporter 2 (SGLT2) inhibitors is now known to decrease cardiovascular morbidity and mortality in type 2 diabetes. However, whether SGLT2 inhibition attenuates vascular aging is unknown. We first confirmed in a cohort of adult subjects that aging is associated with impaired endothelial function and increased arterial stiffness and that these two variables are inversely correlated. Next, we investigated whether SGLT2 inhibition with empagliflozin (Empa) ameliorates endothelial dysfunction and reduces arterial stiffness in aged mice with confirmed vascular dysfunction. Specifically, we assessed mesenteric artery endothelial function and stiffness (via flow-mediated dilation and pressure myography mechanical responses, respectively) and aortic stiffness (in vivo via pulse wave velocity and ex vivo via atomic force microscopy) in Empa-treated (14 mg/kg/day for 6 weeks) and control 80-week-old C57BL/6 J male mice. We report that Empa-treated mice exhibited improved mesenteric endothelial function compared with control, in parallel with reduced mesenteric artery and aortic stiffness. Additionally, Empa-treated mice had greater vascular endothelial nitric oxide synthase activation, lower phosphorylated cofilin, and filamentous actin content, with downregulation of pathways involved in production of reactive oxygen species. Our findings demonstrate that Empa improves endothelial function and reduces arterial stiffness in a preclinical model of aging, making SGLT2 inhibition a potential therapeutic alternative to reduce the progression of CVD in older individuals. Graphical abstract

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

From quartz curvature to late Holocene mobility at Spring Cave, Western Cape, South Africa - Benjamin Davies; Matthew J. Douglass; David R. Braun; John Parkington; Mitchell J. Power; J. Tyler Faith (Archaeological and Anthropological Sciences, 2022)

The 16th Workshop on Antarctic Meteorology and Climate and 6th Year of Polar Prediction in the Southern Hemisphere Meeting - David H. Bromwich; Matthew A. Lazzara; Arthur M. Cayette; Jordan G. Powers; Kirstin Werner; John J. Cassano; Steven R. Colwell; Scott Carpentier; Xun Zou (Advances in Atmospheric Sciences, 2022)

The influence of thermal cues on the reproductive phenology of S ilver S hiner, Notropis photogenis - Jacob Burbank; D. Andrew R. Drake; Michael Power (Journal of Fish Biology, 2022)
Reproductive phenology and the length of the growing season vary in response to interannual environmental variability, with implications for population dynamics of freshwater fishes. Understanding the reproductive phenology of imperilled species in relation to environmental conditions is needed to better evaluate potential responses to changing environmental conditions, estimate future population dynamics and develop comprehensive recovery strategies. We examined Silver Shiner, a species listed as “Threatened” under Canada's Species at Risk Act , during spring 2018 and 2019 to better understand the reproductive phenology of the species at the northern edge of its range in Canada. The initiation of Silver Shiner spawning occurred on the descending limb of the hydrograph and was completed before the onset of the extended period of low summer flow. In addition, both the initiation and cessation of spawning occurred in response to a cumulative growing degree day base 5 (GDD 5 ) cue, with logistic regression models indicating a 50% probability the population initiated and ceased spawning when GDD 5 reached 68°C•days and 368°C•days, respectively. Logistic regression incorporating GDD 5 effectively predicted spawning initiation and cessation, providing useful models for examining the impacts of alterations to the thermal regime on reproductive phenology and improving the ability to evaluate changes in the larval growth period. Furthermore, the models can facilitate the development of real‐time estimates of spawning activity, and therefore ensure that disturbance to the species is minimized during the sensitive reproductive period.

Birds of a Feather Eat Plastic Together: High Levels of Plastic Ingestion in Great Shearwater Adults and Juveniles Across Their Annual Migratory Cycle - Anna R. Robuck; Christine A. Hudak; Lindsay Agvent; Gwenyth Emery; Peter G. Ryan; Vonica Perold; Kevin D. Powers; Johanna Pedersen; Michael A. Thompson; Justin J. Suca; Michael J. Moore; Craig A. Harms; et al. (Frontiers in Marine Science, 2022)
Limited work to date has examined plastic ingestion in highly migratory seabirds like Great Shearwaters ( Ardenna gravis ) across their entire migratory range. We examined 217 Great Shearwaters obtained from 2008–2019 at multiple locations spanning their yearly migration cycle across the Northwest and South Atlantic to assess accumulation of ingested plastic as well as trends over time and between locations. A total of 2328 plastic fragments were documented in the ventriculus portion of the gastrointestinal tract, with an average of 9 plastic fragments per bird. The mass, count, and frequency of plastic occurrence (FO) varied by location, with higher plastic burdens but lower FO in South Atlantic adults and chicks from the breeding colonies. No fragments of the same size or morphology were found in the primary forage fish prey, the Sand Lance ( Ammodytes spp., n = 202) that supports Great Shearwaters in Massachusetts Bay, United States, suggesting the birds directly ingest the bulk of their plastic loads rather than accumulating via trophic transfer. Fourier-transform infrared spectroscopy indicated that low- and high-density polyethylene were the most common polymers ingested, within all years and locations. Individuals from the South Atlantic contained a higher proportion of larger plastic items and fragments compared to analogous life stages in the NW Atlantic, possibly due to increased use of remote, pelagic areas subject to reduced inputs of smaller, more diverse, and potentially less buoyant plastics found adjacent to coastal margins. Different signatures of polymer type, size, and category between similar life stages at different locations suggests rapid turnover of ingested plastics commensurate with migratory stage and location, though more empirical evidence is needed to ground-truth this hypothesis. This work is the first to comprehensively measure the accumulation of ingested plastics by Great Shearwaters over the last decade and across multiple locations spanning their yearly trans-equatorial migration cycle and underscores their utility as sentinels of plastic pollution in Atlantic ecosystems.

Microcoleus (Cyanobacteria) form watershed‐wide populations without strong gradients in population structure - Keith Bouma‐Gregson; Alexander Crits‐Christoph; Mathew R. Olm; Mary E. Power; Jillian F. Banfield (Molecular Ecology, 2022)
The relative importance of separation by distance and by environment to population genetic diversity can be conveniently tested in river networks, where these two drivers are often independently distributed over space. To evaluate the importance of dispersal and environmental conditions in shaping microbial population structures, we performed genome‐resolved metagenomic analyses of benthic Microcoleus ‐dominated cyanobacterial mats collected in the Eel and Russian River networks (California, USA). The 64 Microcoleus genomes were clustered into three species that shared >96.5% average nucleotide identity (ANI). Most mats were dominated by one strain, but minor alleles within mats were often shared, even over large spatial distances (>300 km). Within the most common Microcoleus species, the ANI between the dominant strains within mats decreased with increasing spatial separation. However, over shorter spatial distances (tens of kilometres), mats from different subwatersheds had lower ANI than mats from the same subwatershed, suggesting that at shorter spatial distances environmental differences between subwatersheds in factors like canopy cover, conductivity, and mean annual temperature decreases ANI. Since mats in smaller creeks had similar levels of nucleotide diversity ( π ) as mats in larger downstream subwatersheds, within‐mat genetic diversity does not appear to depend on the downstream accumulation of upstream‐derived strains. The four‐gamete test and sequence length bias suggest recombination occurs between almost all strains within each species, even between populations separated by large distances or living in different habitats. Overall, our results show that, despite some isolation by distance and environmental conditions, sufficient gene‐flow occurs among cyanobacterial strains to prevent either driver from producing distinctive population structures across the watershed.

Earlier snow melt and reduced summer precipitation alter floral traits important to pollination - John M. Powers; Heather M. Briggs; Rachel G. Dickson; Xinyu Li; Diane R. Campbell (Global Change Biology, 2022)
Climate change can cause changes in expression of organismal traits that influence fitness. In flowering plants, floral traits can respond to drought, and that phenotypic plasticity has the potential to affect pollination and plant reproductive success. Global climate change is leading to earlier snow melt in snow‐dominated ecosystems as well as affecting precipitation during the growing season, but the effects of snow melt timing on floral morphology and rewards remain unknown. We conducted crossed manipulations of spring snow melt timing (early vs. control) and summer monsoon precipitation (addition, control, and reduction) that mimicked recent natural variation, and examined plastic responses in floral traits of Ipomopsis aggregata over 3 years in the Rocky Mountains. We tested whether increased summer precipitation compensated for earlier snow melt, and if plasticity was associated with changes in soil moisture and/or leaf gas exchange. Lower summer precipitation decreased corolla length, style length, corolla width, sepal width, and nectar production, and increased nectar concentration. Earlier snow melt (taking into account natural and experimental variation) had the same effects on those traits and decreased inflorescence height. The effect of reduced summer precipitation was stronger in earlier snow melt years for corolla length and sepal width. Trait reductions were explained by drier soil during the flowering period, but this effect was only partially explained by how drier soils affected plant water stress, as measured by leaf gas exchange. We predicted the effects of plastic trait changes on pollinator visitation rates, pollination success, and seed production using prior studies on I. aggregata . The largest predicted effect of drier soil on relative fitness components via plasticity was a decrease in male fitness caused by reduced pollinator rewards (nectar production). Early snow melt and reduced precipitation are strong drivers of phenotypic plasticity, and both should be considered when predicting effects of climate change on plant traits in snow‐dominated ecosystems.

Counting Carbon: Quantifying Biomass in the McMurdo Dry Valleys through Orbital & Field Observations - Mark R. Salvatore; John E. Barrett; Schuyler R. Borges; Sarah N. Power; Lee F. Stanish; Eric R. Sokol; Michael N. Gooseff (International Journal of Remote Sensing, 2021)

Integrating Ecological Stoichiometry to Understand Nutrient Limitation and Potential for Competition in Mixed Pasture Assemblages - K. R. Ball; S. J. Woodin; S. A. Power; C. Brien; B. Berger; P. Smith; E. Pendall (Journal of Soil Science and Plant Nutrition, 2021)

Estimating and Applying Fish and Invertebrate Density and Production Enhancement from Seagrass, Salt Marsh Edge, and Oyster Reef Nursery Habitats in the Gulf of Mexico - Philine S. E. zu Ermgassen; Bryan DeAngelis; Jonathan R. Gair; Sophus zu Ermgassen; Ronald Baker; Andre Daniels; Timothy C. MacDonald; Kara Meckley; Sean Powers; Marta Ribera; Lawrence P. Rozas; Jonathan H. Grabowski (Estuaries and Coasts, 2021)
Seagrasses, oyster reefs, and salt marshes are critical coastal habitats that support high densities of juvenile fish and invertebrates. Yet which species are enhanced through these nursery habitats, and to what degree, remains largely unquantified. Densities of young-of-year fish and invertebrates in seagrasses, oyster reefs, and salt marsh edges as well as in paired adjacent unstructured habitats of the northern Gulf of Mexico were compiled. Species consistently found at higher densities in the structured habitats were identified, and species-specific growth and mortality models were applied to derive production enhancement estimates arising from this enhanced density. Enhancement levels for fish and invertebrate production were similar for seagrass (1370 [SD 317] g m –2 y –1 for 25 enhanced species) and salt marsh edge habitats (1222 [SD 190] g m –2 y –1 , 25 spp.), whereas oyster reefs produced ~650 [SD 114] g m –2 y –1 (20 spp). This difference was partly due to lower densities of juvenile blue crab ( Callinectes sapidus ) on oyster reefs, although only oyster reefs enhanced commercially valuable stone crabs ( Menippe spp.). The production estimates were applied to Galveston Bay, Texas, and Pensacola Bay, Florida, for species known to recruit consistently in those embayments. These case studies illustrated variability in production enhancement by coastal habitats within the northern Gulf of Mexico. Quantitative estimates of production enhancement within specific embayments can be used to quantify the role of essential fish habitat, inform management decisions, and communicate the value of habitat protection and restoration.

The representativeness of the dental calculus dietary record: insights from Taï chimpanzee faecal phytoliths - Robert C. Power; Roman M. Wittig; Jeffery R. Stone; Kornelius Kupczik; Ellen Schulz-Kornas (Archaeological and Anthropological Sciences, 2021)
In recent years, new applications of microremain dietary analysis using dental calculus as a source of dietary data on ancient human subsistence and behaviours have accelerated. The dental calculus of contemporary human and non-human populations with known diets have been used as reference datasets, including the chimpanzees of Taï National Park (Côte d'Ivoire), but explaining the preservation mechanism involved is challenged by our incomplete knowledge of the microremain content within the diets of these reference populations and our rudimentary information on microremain incorporation into dental calculus. Here, we analyse phytoliths in faecal samples to assess to what extent plant phytoliths of a diet are reflected in the dental calculus as well as in the egested faeces. In this study, we identify and document the faecal phytolith assemblages as an indicator of plant consumption in two Western chimpanzees of the Taï National Park (Côte d'Ivoire) before (wet season), during (dry season) and after (dry season) a dust-rich period. Moreover, observational dietary records of these two individuals were compiled to improve the interpretability of this dental calculus phytolith dataset. The faecal phytolith assemblages vary significantly across samples in terms of abundance and diversity. The most common phytolith morphotypes were eudicot plates, single-cell and multi-cell tracheids, monocot rugulose and echinate spheroids and, to a lesser extent, unspecified thick and thin elongates. High loads of grit and other micro-remains (e.g. diatoms) are found during the dry period. Using observational dietary records as a starting point and our faecal results as a terminus, we consider how dental calculus can accumulate phytoliths. Our findings enable identification of the phytolith morphotypes that are under-represented in dental calculus, which is highly informative for future dental calculus research strategies.

Diet overlap of common and at-risk riverine benthic fishes before and after Round Goby (Neogobius melanostomus) invasion - B. L. Firth; M. S. Poesch; M. A. Koops; D. A. R. Drake; M. Power (Biological Invasions, 2021)

A Marine Biodiversity Observation Network for Genetic Monitoring of Hard-Bottom Communities (ARMS-MBON) - Matthias Obst; Katrina Exter; A. Louise Allcock; Christos Arvanitidis; Alizz Axberg; Maria Bustamante; Ibon Cancio; Diego Carreira-Flores; Eva Chatzinikolaou; Giorgos Chatzigeorgiou; Nathan Chrismas; Melody S. Clark; et al. (Frontiers in Marine Science, 2020)
Marine hard-bottom communities are undergoing severe change under the influence of multiple drivers, notably climate change, extraction of natural resources, pollution and eutrophication, habitat degradation, and invasive species. Monitoring marine biodiversity in such habitats is, however, challenging as it typically involves expensive, non-standardized, and often destructive sampling methods that limit its scalability. Differences in monitoring approaches furthermore hinders inter-comparison among monitoring programs. Here, we announce a Marine Biodiversity Observation Network (MBON) consisting of Autonomous Reef Monitoring Structures (ARMS) with the aim to assess the status and changes in benthic fauna with genomic-based methods, notably DNA metabarcoding, in combination with image-based identifications. This article presents the results of a 30-month pilot phase in which we established an operational and geographically expansive ARMS-MBON. The network currently consists of 20 observatories distributed across European coastal waters and the polar regions, in which 134 ARMS have been deployed to date. Sampling takes place annually, either as short-term deployments during the summer or as long-term deployments starting in spring. The pilot phase was used to establish a common set of standards for field sampling, genetic analysis, data management, and legal compliance, which are presented here. We also tested the potential of ARMS for combining genetic and image-based identification methods in comparative studies of benthic diversity, as well as for detecting non-indigenous species. Results show that ARMS are suitable for monitoring hard-bottom environments as they provide genetic data that can be continuously enriched, re-analyzed, and integrated with conventional data to document benthic community composition and detect non-indigenous species. Finally, we provide guidelines to expand the network and present a sustainability plan as part of the European Marine Biological Resource Centre ( www.embrc.eu ).

Estimating microbial mat biomass in the McMurdo Dry Valleys, Antarctica using satellite imagery and ground surveys - Sarah N. Power; Mark R. Salvatore; Eric R. Sokol; Lee F. Stanish; J. E. Barrett (Polar Biology, 2020)

Ecometrics and the paleoecological implications of Pleistocene faunas from the western coastal plains of the Cape Floristic Region, South Africa - J. Tyler Faith; David R. Braun; Benjamin Davies; Larisa R. G. DeSantis; Matthew J. Douglass; Irene Esteban; Vincent Hare; Naomi E. Levin; Julie Luyt; Robyn Pickering; Mitchell J. Power; Judith Sealy; et al. (Journal of Quaternary Science, 2020)
The Pleistocene ungulate communities from the western coastal plains of South Africa's Cape Floristic Region (CFR) are diverse and dominated by grazers, in contrast to the region's Holocene and historical faunas, which are relatively species‐poor and dominated by small‐bodied browsers and mixed feeders. An expansion of grassy habitats is clearly implied by the Pleistocene faunas, but the presence of ruminant grazers that cannot survive the summer dry season typical of the region today suggests other important paleoecological changes. Here we use dental ecometrics to explore the paleoecological implications of the region's Pleistocene faunas. We show that the dental traits (hypsodonty and occlusal topography) of the ungulates that occurred historically in the CFR track annual and summer aridity, and we use these relationships to reconstruct past aridity. Our results indicate that the Pleistocene faunas signal paleoenvironments that were on average less arid than today, including during the summer, consistent with other lines of evidence that suggest a higher water table and expansion of well‐watered habitats. Greater water availability can be explained by lower temperature and reduced evapotranspiration during cooler phases of the Pleistocene, probably coupled with enhanced groundwater recharge due to increased winter precipitation.

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

The 13th and 14th Workshops on Antarctic Meteorology and Climate - Matthew A. Lazzara; Sophie A. Orendorf; Taylor P. Norton; Jordan G. Powers; David H. Bromwich; Scott Carpentier; John J. Cassano; Steven R. Colwell; Arthur M. Cayette; Kirstin Werner (Advances in Atmospheric Sciences, 2020)

Evaluation of Australian Tsunami Warning Thresholds Using Inundation Modelling - Diana J. M. Greenslade; Burak Uslu; Stewart C. R. Allen; Claire L. Kain; Kaya M. Wilson; Hannah E. Power (Pure and Applied Geophysics, 2020)

Effect of Shallow Slip Amplification Uncertainty on Probabilistic Tsunami Hazard Analysis in Subduction Zones: Use of Long-Term Balanced Stochastic Slip Models - A. Scala; S. Lorito; F. Romano; S. Murphy; J. Selva; R. Basili; A. Babeyko; A. Herrero; A. Hoechner; F. Løvholt; F. E. Maesano; P. Perfetti; et al. (Pure and Applied Geophysics, 2020)

The Presence of a High Peak Feature Within Low-Average Shear Stimuli Induces Quiescence in Venous Endothelial Cells - M. Franzoni; D. T. O’Connor; L. Marcar; D. Power; M. A. Moloney; E. G. Kavanagh; R. L. Leask; J. Nolan; P. A. Kiely; M. T. Walsh (Annals of Biomedical Engineering, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

DIBI, a novel 3-hydroxypyridin-4-one chelator iron-binding polymer, inhibits breast cancer cell growth and functions as a chemosensitizer by promoting S-phase DNA damage - Anna L. Greenshields; Melanie R. Power Coombs; Wasundara Fernando; Bruce E. Holbein; David W. Hoskin (BioMetals, 2019)

Effects of dry‐season irrigation on leaf physiology and biomass allocation in tropical lianas and trees - Chris M. Smith‐Martin; Carolina L. Bastos; Omar R. Lopez; Jennifer S. Powers; Stefan A. Schnitzer (Ecology, 2019)
Lianas are more abundant in seasonal forests than in wetter forests and are thought to perform better than trees when light is abundant and water is limited. We tested the hypothesis that lianas perform better than trees during seasonal drought using a common garden experiment with 12 taxonomically diverse species (six liana and six tree species) in 12 replicated plots. We irrigated six of the plots during the dry season for four years, while the remaining six control plots received only ambient rainfall. In year 5, we measured stem diameters for all individuals and harvested above‐ and belowground biomass for a subset of individuals to quantify absolute growth and biomass allocation to roots, stems, and leaves, as well as total root length and maximum rooting depth. We also measured rate of photosynthesis, intrinsic water use efficiency ( iWUE ), pre‐dawn and midday water potential, and a set of functional and hydraulic traits. During the peak of the dry season, lianas in control plots had 54% higher predawn leaf water potentials (Ψ PD ), and 45% higher photosynthetic rates than trees in control plots. By contrast, during the peak of the wet season, these physiological differences between lianas and trees become less pronounced and, in some cases, even disappeared. Trees had higher specific leaf area ( SLA ) than lianas; however, no other functional trait differed between growth forms. Trees responded to the irrigation treatment with 15% larger diameters and 119% greater biomass than trees in control plots. Liana growth, however, did not respond to irrigation; liana diameter and biomass were similar in control and irrigation plots, suggesting that lianas were far less limited by soil moisture than were trees. Contrary to previous hypotheses, lianas did not have deeper roots than trees; however, lianas had longer roots per stem diameter than did trees. Our results support the hypothesis that lianas perform better and experience less physiological stress than trees during seasonal drought, suggesting clear differences between growth forms in response to altered rainfall regimes. Ultimately, better dry‐season performance may explain why liana abundance peaks in seasonal forests compared to trees, which peak in abundance in less seasonal, wetter forests.

A framework to measure the wildness of managed large vertebrate populations - Matthew F. Child; S. A. Jeanetta Selier; Frans G. T. Radloff; W. Andrew Taylor; Michael Hoffmann; Lizanne Nel; R. John Power; Coral Birss; Nicola C. Okes; Michael J. Peel; David Mallon; Harriet Davies‐Mostert (Conservation Biology, 2019)
As landscapes continue to fall under human influence through habitat loss and fragmentation, fencing is increasingly being used to mitigate anthropogenic threats and enhance the commercial value of wildlife. Subsequent intensification of management potentially erodes wildness by disembodying populations from landscape‐level processes, thereby disconnecting species from natural selection. Tools are needed to measure the degree to which populations of large vertebrate species in formally protected and privately owned wildlife areas are self‐sustaining and free to adapt. We devised a framework to measure such wildness based on 6 attributes relating to the evolutionary and ecological dynamics of vertebrates (space, disease and parasite resistance, exposure to predation, exposure to limitations and fluctuations of food and water supply, and reproduction). For each attribute, we set empirical, species‐specific thresholds between 5 wildness states based on quantifiable management interventions. We analysed data from 205 private wildlife properties with management objectives spanning ecotourism to consumptive utilization to test the framework on 6 herbivore species representing a range of conservation statuses and commercial values. Wildness scores among species differed significantly, and the proportion of populations identified as wild ranged from 12% to 84%, which indicates the tool detected site‐scale differences both among populations of different species and populations of the same species under different management regimes. By quantifying wildness, this framework provides practitioners with standardized measurement units that link biodiversity with the sustainable use of wildlife. Applications include informing species management plans at local scales; standardizing the inclusion of managed populations in red‐list assessments; and providing a platform for certification and regulation of wildlife‐based economies. Applying this framework may help embed wildness as a normative value in policy and mitigate the shifting baseline of what it means to truly conserve a species.

Short-interval intracortical inhibition to the biceps brachii is present during arm cycling but is not different than a position- and intensity-matched tonic contraction - L. R. Alcock; A. J. Spence; E. J. Lockyer; D. C. Button; Kevin E. Power (Experimental Brain Research, 2019)

Treatment patterns and survival differ between early-onset and late-onset colorectal cancer patients: the patient outcomes to advance learning network - Andrea N. Burnett-Hartman; J. David Powers; Jessica Chubak; Douglas A. Corley; Nirupa R. Ghai; Carmit K. McMullen; Pamala A. Pawloski; Andrew T. Sterrett; Heather Spencer Feigelson (Cancer Causes & Control, 2019)

Central contributions to torque depression: an antagonist perspective - Caleb T. Sypkes; Vincenzo S. Contento; Leah R. Bent; Chris J. McNeil; Geoffrey A. Power (Experimental Brain Research, 2019)

Bonefish in South Florida: status, threats and research needs - Jacob W. Brownscombe; Andy J. Danylchuk; Aaron J. Adams; Brooke Black; Ross Boucek; Michael Power; Jennifer S. Rehage; Rolando O. Santos; Russ W. Fisher; Bill Horn; Christopher R. Haak; Sean Morton; et al. (Environmental Biology of Fishes, 2019)

Hydrodynamic and isotopic niche differentiation between juveniles of two sympatric cryptic bonefishes, Albula vulpes and Albula goreensis - Christopher R. Haak; Michael Power; Geoffrey W. Cowles; Andy J. Danylchuk (Environmental Biology of Fishes, 2019)

Ontogenetic patterns in resource use dynamics of bonefish (Albula vulpes) in the Bahamas - Karen J. Murchie; Christopher R. Haak; Michael Power; Oliver N. Shipley; Andy J. Danylchuk; Steven J. Cooke (Environmental Biology of Fishes, 2019)

Effects of competition and herbivory over woody seedling growth in a temperate woodland trump the effects of elevated CO2 - L. Collins; M. M. Boer; V. Resco de Dios; S. A. Power; E. R. Bendall; S. Hasegawa; R. Ochoa Hueso; J. Piñeiro Nevado; R. A. Bradstock (Oecologia, 2018)

The 12th Workshop on Antarctic Meteorology and Climate - Matthew A. Lazzara; Jordan G. Powers; Carol A. Costanza; David H. Bromwich; Scott Carpentier; Steve R. Colwell (Advances in Atmospheric Sciences, 2018)

A Meta-analysis of Arsenic Exposure and Lung Function: Is There Evidence of Restrictive or Obstructive Lung Disease? - Tiffany R. Sanchez; Martha Powers; Matthew Perzanowski; Christine M. George; Joseph H. Graziano; Ana Navas-Acien (Current Environmental Health Reports, 2018)

The early inflorescence of Arabidopsis thaliana demonstrates positional effects in floral organ growth and meristem patterning - Andrew R. G. Plackett; Stephen J. Powers; Andy L. Phillips; Zoe A. Wilson; Peter Hedden; Stephen G. Thomas (Plant Reproduction, 2018)

Trophic niche dynamics of three nearshore benthic predators in The Bahamas - Oliver N. Shipley; Karen J. Murchie; Michael G. Frisk; Owen R. O’Shea; Maggie M. Winchester; Edward J. Brooks; Jessie Pearson; Michael Power (Hydrobiologia, 2018)

Experimentally altered rainfall regimes and host root traits affect grassland arbuscular mycorrhizal fungal communities - Coline Deveautour; Suzanne Donn; Sally A. Power; Alison E. Bennett; Jeff R. Powell (Molecular Ecology, 2018)
Future climate scenarios predict changes in rainfall regimes. These changes are expected to affect plants via effects on the expression of root traits associated with water and nutrient uptake. Associated microorganisms may also respond to these new precipitation regimes, either directly in response to changes in the soil environment or indirectly in response to altered root trait expression. We characterized arbuscular mycorrhizal (AM) fungal communities in an Australian grassland exposed to experimentally altered rainfall regimes. We used Illumina sequencing to assess the responses of AM fungal communities associated with four plant species sampled in different watering treatments and evaluated the extent to which shifts were associated with changes in root traits. We observed that altered rainfall regimes affected the composition but not the richness of the AM fungal communities, and we found distinctive communities in the increased rainfall treatment. We found no evidence of altered rainfall regime effects via changes in host physiology because none of the studied traits were affected by changes in rainfall. However, specific root length was observed to correlate with AM fungal richness, while concentrations of phosphorus and calcium in root tissue and the proportion of root length allocated to fine roots were correlated to community composition. Our study provides evidence that climate change and its effects on rainfall may influence AM fungal community assembly, as do plant traits related to plant nutrition and water uptake. We did not find evidence that host responses to altered rainfall drive AM fungal community assembly in this grassland ecosystem.

Molecular testing of adult Pacific salmon and trout ( Oncorhynchus spp.) for several RNA viruses demonstrates widespread distribution of piscine orthoreovirus in Alaska and Washington - M K Purcell; R L Powers; J Evered; J Kerwin; T R Meyers; B Stewart; J R Winton (Journal of Fish Diseases, 2018)
This research was initiated in conjunction with a systematic, multiagency surveillance effort in the United States (U.S.) in response to reported findings of infectious salmon anaemia virus ( ISAV ) RNA in British Columbia, Canada. In the systematic surveillance study reported in a companion paper, tissues from various salmonids taken from Washington and Alaska were surveyed for ISAV RNA using the U.S.‐approved diagnostic method, and samples were released for use in this present study only after testing negative. Here, we tested a subset of these samples for ISAV RNA with three additional published molecular assays, as well as for RNA from salmonid alphavirus ( SAV ), piscine myocarditis virus ( PMCV ) and piscine orthoreovirus ( PRV ). All samples ( n = 2,252; 121 stock cohorts) tested negative for RNA from ISAV , PMCV , and SAV . In contrast, there were 25 stock cohorts from Washington and Alaska that had one or more individuals test positive for PRV RNA ; prevalence within stocks varied and ranged from 2% to 73%. The overall prevalence of PRV RNA ‐positive individuals across the study was 3.4% (77 of 2,252 fish tested). Findings of PRV RNA were most common in coho ( Oncorhynchus kisutch Walbaum) and Chinook ( O. tshawytscha Walbaum) salmon.

Segregation of the amphitelically attached univalent X chromosome in the spittlebug Philaenus spumarius - Kristen D. Felt; Makayla B. Lagerman; Nigel A. Ravida; Lu Qian; Samantha R. Powers; Leocadia V. Paliulis (Protoplasma, 2017)

Thermal pasteurization of ready-to-eat foods and vegetables: Critical factors for process design and effects on quality - Jing Peng; Juming Tang; Diane M. Barrett; Shyam S. Sablani; Nathan Anderson; Joseph R. Powers (Critical Reviews in Food Science and Nutrition, 2017)

Long-term measurements of agronomic crop irrigation made in the Mississippi delta portion of the lower Mississippi River Valley - Joseph H. Massey; C. Mark Stiles; Josh W. Epting; R. Shane Powers; David B. Kelly; Taylor H. Bowling; C. Leighton Janes; Dean A. Pennington (Irrigation Science, 2017)

DIMBOA levels in hexaploid Brazilian wheat are not associated with antibiosis against the cereal aphids Rhopalosiphum padi and Sitobion avenae - Jorge F. Pereira; André L. F. Sarria; Stephen J. Powers; Gudbjorg I. Aradottir; John C. Caulfield; Janet Martin; Lesley E. Smart; John A. Pickett; Michael A. Birkett; Paulo R. V. S. Pereira (Theoretical and Experimental Plant Physiology, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Bioluminescence spectra from three deep-sea polychaete worms - Warren R. Francis; Meghan L. Powers; Steven H. D. Haddock (Marine Biology, 2016)

A keystone ecologist: Robert Treat Paine, 1933–2016 - James A. Estes; Paul K. Dayton; Peter Kareiva; Simon A. Levin; Jane Lubchenco; Bruce A. Menge; Stephen R. Palumbi; Mary E. Power; John Terborgh (Ecology, 2016)
Robert T. Paine, who passed away on 13 June 2016, is among the most influential people in the history of ecology. Paine was an experimentalist, a theoretician, a practitioner, and proponent of the “ecology of place,” and a deep believer in the importance of natural history to ecological understanding. His scientific legacy grew from the discovery of a link between top‐down forcing and species diversity, a breakthrough that led to the ideas of both keystone species and trophic cascades, and to our early understanding of the mosaic nature of biological communities, causes of zonation across physical gradients, and the intermediate‐disturbance hypothesis of species diversity. Paine's influence as a mentor was equally important to the growth of ecological thinking, natural resource conservation, and policy. He served ecology as an Ecological Society of America president, an editor of the Society's journals, a member of and contributor to the National Academy of Sciences and the National Research Council, and an in‐demand advisor to various state and federal agencies. Paine's broad interests, enthusiasm, charisma, and humor deeply affected our lives and the lives of so many others.

The 10th Antarctic meteorological observation, modeling, and forecasting workshop - Steve R. Colwell; Arthur M. Cayette; Matthew A. Lazzara; Jordan G. Powers; David H. Bromwich; John J. Cassano; Scott Carpentier (Advances in Atmospheric Sciences, 2016)

Examining rip current escape strategies in non-traditional beach morphologies - Ben R. Van Leeuwen; R. Jak McCarroll; Robert W. Brander; Ian L. Turner; Hannah E. Power; Anthony J. Bradstreet (Natural Hazards, 2016)

Anthropogenic influence on Amazonian forests in pre‐history: An ecological perspective - Mark B. Bush; Crystal H. McMichael; Dolores R. Piperno; Miles R. Silman; Jos Barlow; Carlos A. Peres; Mitchell Power; Michael W. Palace (Journal of Biogeography, 2015)
An important debate has been re‐invigorated by new data concerning the size and environmental impacts of human populations in the Amazon Basin during pre‐history. Here, we review the history of debates concerning pre‐historic human occupation of the Amazon Basin along with the presentation of empirical data from archaeological and palaeoecological research. The combined evidence suggests that human occupation and resulting influence on Amazonian ecosystems were heterogeneous on both regional and local scales. Pre‐historic occupation sites are more likely to have been located in forests with a pronounced dry season or in forests that are within 15 km of a river floodplain, rather than in ever‐wet forests or in interfluvial regions far removed from large rivers. Forest enrichment of preferred species and game depletion through hunting are most probable within 15 km of an occupation site. Given the spatial and temporal patterning of these data, views of significant Amazonian‐wide cultural impacts on riverine and interfluvial forest are not supported at this time.

An analysis of P seudomonas genomic diversity in take‐all infected wheat fields reveals the lasting impact of wheat cultivars on the soil microbiota - T. H. Mauchline; D. Chedom‐Fotso; G. Chandra; T. Samuels; N. Greenaway; A. Backhaus; V. McMillan; G. Canning; S. J. Powers; K. E. Hammond‐Kosack; P. R. Hirsch; I. M. Clark; et al. (Environmental Microbiology, 2015)
Summary Manipulation of the soil microbiota associated with crop plants has huge promise for the control of crop pathogens. However, to fully realize this potential we need a better understanding of the relationship between the soil environment and the genes and phenotypes that enable microbes to colonize plants and contribute to biocontrol. A recent 2 years of investigation into the effect of wheat variety on second year crop yield in the context of take‐all fungal infection presented the opportunity to examine soil microbiomes under closely defined field conditions. Amplicon sequencing of second year soil samples showed that P seudomonas spp. were particularly affected by the wheat cultivar grown in year one. Consequently, 318 rhizosphere‐associated P seudomonas fluorescens strains were isolated and characterized across a variety of genetic and phenotypic traits. Again, the wheat variety grown in the first year of the study was shown to exert considerable selective pressure on both the extent and nature of P seudomonas genomic diversity. Furthermore, multiple significant correlations were identified within the phenotypic/genetic structure of the Pseudomonas population, and between individual genotypes and the external wheat field environment. The approach outlined here has considerable future potential for our understanding of plant–microbe interactions, and for the broader analysis of complex microbial communities.

Genetic diversity, population structure and phenotypic variation in European Salix viminalis L. (Salicaceae) - S. Berlin; S. O. Trybush; J. Fogelqvist; N. Gyllenstrand; H. R. Hallingbäck; I. Åhman; N-E. Nordh; I. Shield; S. J. Powers; M. Weih; U. Lagercrantz; A-C. Rönnberg-Wästljung; et al. (Tree Genetics & Genomes, 2014)

Metagenetic analysis of patterns of distribution and diversity of marine meiobenthic eukaryotes - Vera G. Fonseca; Gary R. Carvalho; Ben Nichols; Christopher Quince; Harriet F. Johnson; Simon P. Neill; John D. Lambshead; W. Kelley Thomas; Deborah M. Power; Simon Creer (Global Ecology and Biogeography, 2014)
Aim Meiofaunal communities that inhabit the marine benthos offer unique opportunities to simultaneously study the macroecology of numerous phyla that exhibit different life‐history strategies. Here, we ask: (1) if the macroecology of meiobenthic communities is explained mainly by dispersal constraints or by environmental conditions; and (2) if levels of meiofaunal diversity surpass existing estimates based on morphological taxonomy. Location UK and mainland European coast. Methods Next‐generation sequencing techniques ( NGS ; R oche 454 FLX platform) using 18S nuclear small subunit ribosomal DNA ( rDNA ) gene. Pyrosequences were analysed using A mplicon N oise followed by chimera removal using P erseus . Results Rarefaction curves revealed that sampling saturation was only reached at 15% of sites, highlighting that the bulk of meiofaunal diversity is yet to be discovered. Overall, 1353 OTU s were recovered and assigned to 23 different phyla. The majority of sampled sites had c. 60–70 unique operational taxonomic units ( OTU s) per site, indicating high levels of beta diversity. The environmental parameters that best explained community structure were seawater temperature, geographical distance and sediment size, but most of the variability ( R 2 = 70%–80%) remains unexplained. Main conclusions High percentages of endemic OTU s suggest that meiobenthic community composition is partly niche‐driven, as observed in larger organisms, but also shares macroecological features of microorganisms by showing high levels of cosmopolitanism (albeit on a much smaller scale). Meiobenthic communities exhibited patterns of isolation by distance as well as associations between niche, latitude and temperature, indicating that meiobenthic communities result from a combination of niche assembly and dispersal processes. Conversely, isolation‐by‐distance patterns were not identified in the featured protists, suggesting that animals and protists adhere to radically different macroecological processes, linked to life‐history strategies.

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

The Role of Nitrogen Deposition in Widespread Plant Community Change Across Semi-natural Habitats - Chris D. Field; Nancy B. Dise; Richard J. Payne; Andrea J. Britton; Bridget A. Emmett; Rachel C. Helliwell; Steve Hughes; Laurence Jones; Steven Lees; Jonathan R. Leake; Ian D. Leith; Gareth K. Phoenix; et al. (Ecosystems, 2014)

Characterization of the DYX2 locus on chromosome 6p22 with reading disability, language impairment, and IQ - John D. Eicher; Natalie R. Powers; Laura L. Miller; Kathryn L. Mueller; Sara Mascheretti; Cecilia Marino; Erik G. Willcutt; John C. DeFries; Richard K. Olson; Shelley D. Smith; Bruce F. Pennington; J. Bruce Tomblin; et al. (Human Genetics, 2014)

Human and Non-Human Primate Intestinal FcRn Expression and Immunoglobulin G Transcytosis - Pamela J. Hornby; Philip R. Cooper; Connie Kliwinski; Edwin Ragwan; John R. Mabus; Benjamin Harman; Suzanne Thompson; Amanda L. Kauffman; Zhengyin Yan; Susan H. Tam; Haimanti Dorai; Gordon D. Powers; et al. (Pharmaceutical Research, 2014)

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Head Impact Exposure in Youth Football: Elementary School Ages 9–12 Years and the Effect of Practice Structure - Bryan R. Cobb; Jillian E. Urban; Elizabeth M. Davenport; Steven Rowson; Stefan M. Duma; Joseph A. Maldjian; Christopher T. Whitlow; Alexander K. Powers; Joel D. Stitzel (Annals of Biomedical Engineering, 2013)

Food webs in Mediterranean rivers - Mary E. Power; Joseph R. Holomuzki; Rex L. Lowe (Hydrobiologia, 2013)

Investigation of the persistence of rafoxanide residues in bovine milk and fate during processing - C. Power; M. Danaher; R. Sayers; B. O’Brien; M. Whelan; A. Furey; K. Jordan (Food Additives & Contaminants: Part A, 2013)

Investigation of the persistence of triclabendazole residues in bovine milk following lactating-cow and dry-cow treatments - C. Power; M. Whelan; M. Danaher; Y. Bloemhoff; R. Sayers; B. O’Brien; A. Furey; K. Jordan (Food Additives & Contaminants: Part A, 2013)

The effects of visual training on multisensory temporal processing - Ryan A. Stevenson; Magdalena M. Wilson; Albert R. Powers; Mark T. Wallace (Experimental Brain Research, 2013)

Genetic influences of resting state fMRI activity in language-related brain regions in healthy controls and schizophrenia patients: a pilot study - Sharna Jamadar; Natalie R. Powers; Shashwath A. Meda; Vince D. Calhoun; Joel Gelernter; Jeffrey R. Gruen; Godfrey D. Pearlson (Brain Imaging and Behavior, 2013)

Thyroid disruption in the lizard Podarcis bocagei exposed to a mixture of herbicides: a field study - Rita C. Bicho; Maria José Amaral; Augusto M. R. Faustino; Deborah M. Power; Alexandra Rêma; Miguel A. Carretero; Amadeu M. V. M. Soares; Reinier M. Mann (Ecotoxicology, 2013)

Effects of an exercise and hypocaloric healthy eating program on biomarkers associated with long-term prognosis after early-stage breast cancer: a randomized controlled trial - E. Scott; A. J. Daley; H. Doll; N. Woodroofe; R. E. Coleman; N. Mutrie; H. Crank; H. J. Powers; J. M. Saxton (Cancer Causes & Control, 2013)

Spring climate and summer otolith growth in juvenile Arctic charr, Salvelinus alpinus - J. A. Godiksen; R. Borgstrøm; J. B. Dempson; J. Kohler; H. Nordeng; M. Power; A. Stien; M.-A. Svenning (Environmental Biology of Fishes, 2012)

Molecular and cellular changes in skin and muscle during metamorphosis of Atlantic halibut (Hippoglossus hippoglossus) are accompanied by changes in deiodinases expression - M. A. Campinho; M. Galay-Burgos; N. Silva; R. A. Costa; R. N. Alves; G. E. Sweeney; D. M. Power (Cell and Tissue Research, 2012)

Long‐term nitrogen additions increase likelihood of climate stress and affect recovery from wildfire in a lowland heath - Georgina E. Southon; Emma R. Green; Alan G. Jones; Chris G. Barker; Sally A. Power (Global Change Biology, 2012)
Increases in the emissions and associated atmospheric deposition of nitrogen (N) have the potential to cause significant changes to the structure and function of N‐limited ecosystems. Here, we present the results of a long‐term (13 year) experiment assessing the impacts of N addition (30 kg ha −1 yr −1 ) on a UK lowland heathland under a wide range of environmental conditions, including the occurrence of prolonged natural drought episodes and a severe summer fire. Our findings indicate that elevated N deposition results in large, persistent effects on Calluna growth, phenology and chemistry, severe suppression of understorey lichen flora and changes in soil biogeochemistry. Growing season rainfall was found to be a strong driver of inter‐annual variation in Calluna growth and, although interactions between N and rainfall for shoot growth were not significant until the later phase of the experiment, N addition exacerbated the extent of drought injury to Calluna shoots following naturally occurring droughts in 2003 and 2009. Following a severe wildfire at the experimental site in 2006, heathland regeneration dynamics were significantly affected by N, with a greater abundance of pioneering moss species and suppression of the lichen flora in plots receiving N additions. Significant interactions between climate and N were also apparent post fire, with the characteristic stimulation in Calluna growth in +N plots suppressed during dry years. Carbon (C) and N budgets demonstrate large increases in both above‐ and below‐ground stocks of these elements in N‐treated plots prior to the fire, despite higher levels of soil microbial activity and organic matter turnover. Although much of the organic material was removed during the fire, pre‐existing treatment differences were still evident following the burn. Post fire accumulation of below‐ground C and N stocks was increased rapidly in N‐treated plots, highlighting the role of N deposition in ecosystem C sequestration.

Engineering gibberellin metabolism in Solanum nigrum L. by ectopic expression of gibberellin oxidase genes - A. Bhattacharya; D. A. Ward; P. Hedden; A. L. Phillips; J. B. Power; M. R. Davey (Plant Cell Reports, 2012)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Non-cancer endpoints in BRCA1/2 carriers after risk-reducing salpingo-oophorectomy - J. V. Cohen; L. Chiel; L. Boghossian; M. Jones; J. E. Stopfer; J. Powers; T. R. Rebbeck; K. L. Nathanson; S. M. Domchek (Familial Cancer, 2012)

Intra-operative washing of morcellised bone allograft with pulse lavage: how effective is it in reducing blood and marrow content? - T. Ibrahim; A. Qureshi; T. A. McQuillan; J. Thomson; G. Galea; R. A. Power (Cell and Tissue Banking, 2012)

Does Ischemia Contribute to Energy Failure in Severe TBI? - Michael N. Diringer; Allyson R. Zazulia; William J. Powers (Translational Stroke Research, 2011)

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Red snapper management in the Gulf of Mexico: science- or faith-based? - J. H. Cowan; C. B. Grimes; W. F. Patterson; C. J. Walters; A. C. Jones; W. J. Lindberg; D. J. Sheehy; W. E. Pine; J. E. Powers; M. D. Campbell; K. C. Lindeman; S. L. Diamond; et al. (Reviews in Fish Biology and Fisheries, 2011)

Stable isotope-based determinations of the average temperatures experienced by young-of-the-year Svalbard Arctic charr (Salvelinus alpinus (L.)) - J. A. Godiksen; M.-A. Svenning; R. N. Sinnatamby; J. B. Dempson; R. Borgstrøm; M. Power (Polar Biology, 2011)

Expression of the myosin light chains 1, 2 and 3 in the muscle of blackspot seabream (Pagellus bogaraveo, Brunnich), during development - P. Silva; D. M. Power; L. M. P. Valente; N. Silva; R. A. F. Monteiro; E. Rocha (Fish Physiology and Biochemistry, 2010)

Epidemiology of non-multiresistant methicillin-resistant Staphylococcus aureus infection in Queensland, Australia: associations with indigenous populations and Panton–Valentine leukocidin - G. R. Nimmo; J. M. Schooneveldt; J. L. Sutherland; S. Power; D. Olesen; C. Selvey; F. Beard; M. Jones; D. L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

High frequency direct plant regeneration from leaf and petals of Cape Primrose (Streptocarpus) - A. Chaudhury; J. B. Power; M. R. Davey (Journal of Crop Science and Biotechnology, 2010)

Ultrasequencing of the meiofaunal biosphere: practice, pitfalls and promises - S. CREER; V. G. FONSECA; D. L. PORAZINSKA; R. M. GIBLIN‐DAVIS; W. SUNG; D. M. POWER; M. PACKER; G. R. CARVALHO; M. L. BLAXTER; P. J. D. LAMBSHEAD; W. K. THOMAS (Molecular Ecology, 2010)
Biodiversity assessment is the key to understanding the relationship between biodiversity and ecosystem functioning, but there is a well‐acknowledged biodiversity identification gap related to eukaryotic meiofaunal organisms. Meiofaunal identification is confounded by the small size of taxa, morphological convergence and intraspecific variation. However, the most important restricting factor in meiofaunal ecological research is the mismatch between diversity and the number of taxonomists that are able to simultaneously identify and catalogue meiofaunal diversity. Accordingly, a molecular operational taxonomic unit (MOTU)‐based approach has been advocated for en mass meiofaunal biodiversity assessment, but it has been restricted by the lack of throughput afforded by chain termination sequencing. Contemporary pyrosequencing offers a solution to this problem in the form of environmental metagenetic analyses, but this represents a novel field of biodiversity assessment. Here, we provide an overview of meiofaunal metagenetic analyses, ranging from sample preservation and DNA extraction to PCR, sequencing and the bioinformatic interrogation of multiple, independent samples using 454 Roche sequencing platforms. We report two examples of environmental metagenetic nuclear small subunit 18S (nSSU) analyses of marine and tropical rainforest habitats and provide critical appraisals of the level of putative recombinant DNA molecules (chimeras) in metagenetic data sets. Following stringent quality control measures, environmental metagenetic analyses achieve MOTU formation across the eukaryote domain of life at a fraction of the time and cost of traditional approaches. The effectiveness of Roche 454 sequencing brings substantial advantages to studies aiming to elucidate the molecular genetic richness of not only meiofaunal, but also all complex eukaryotic communities.

Collaborative Problem Solving Using an Industrial Ecology Approach - Susan E. Boehme; Marta A. Panero; Gabriela R. Muñoz; Charles W. Powers; Sandra N. Valle (Journal of Industrial Ecology, 2009)
Summary Over the course of ten years, a consortium of stakeholders (the Harbor Consortium) used a collaborative approach to identify viable pollution prevention (P2) strategies for specific contaminants, namely mercury, cadmium, polychlorinated biphenyls (PCBs), dioxins, and polycyclic aromatic hydrocarbons (PAHs) as well as suspended solids entering the New York/New Jersey Harbor. The project, titled “The New York/New Jersey Harbor Watershed Pollution Prevention and Industrial Ecology Project,” in a very conscious and overt way engaged stakeholders in the process of developing P2 recommendations for the Harbor. The industrial ecology (IE) tools applied by the Harbor Consortium include substance flow analysis (SFA), material flow analysis (MFA), and, to a limited extent, life cycle analysis (LCA) and fate and transport analysis (F&T), to quantify and characterize how the contaminants flow through the regional economy and the Harbor Watershed once released to the environment. The application of these scientific tools to five contaminants at such a large geographical scale, within the context of a broad and inclusive stakeholder process, and with the goal of identifying and implementing pollution prevention strategies, led to a wide range of surprising outcomes and lessons learned. Undertaking this IE research with the key institutions and stakeholders at the table resulted in the identification and the implementation of many P2 opportunities.

Ungulate Carcasses Perforate Ecological Filters and Create Biogeochemical Hotspots in Forest Herbaceous Layers Allowing Trees a Competitive Advantage - Joseph K. Bump; Christopher R. Webster; John A. Vucetich; Rolf O. Peterson; Joshua M. Shields; Matthew D. Powers (Ecosystems, 2009)

Phylogeography and sympatric differentiation of the Arctic charr Salvelinus alpinus (L.) complex in Siberia as revealed by mtDNA sequence analysis - S. S. Alekseyev; R. Bajno; N. V. Gordeeva; J. D. Reist; M. Power; A. F. Kirillov; V. P. Samusenok; A. N. Matveev (Journal of Fish Biology, 2009)
Sequence variation in the mtDNA control region of Arctic charr Salvelinus alpinus and Dolly Varden Salvelinus malma from 56 Siberian and North American populations was analysed to assess their phylogeographic relationships and the origins of sympatric forms. Phylogenetic trees confirm the integrity of phylogroups reported in previous mtDNA studies except that the Siberian group does not separate as a single cluster. Haplotype network analysis indicates the proximity of Siberian and Atlantic haplotypes. These are considered as one Eurasian group represented by the Atlantic, east Siberian (interior Siberia including Transbaikalia, Taimyr) and Eurosiberian (Finland, Spitsbergen, Taimyr) sub‐groups. Salvelinus alpinus with presumably introgressed Bering group (malma) haplotypes were found along eastern Siberian coasts up to the Olenek Bay and the Lena Delta region, where they overlap with the Eurasian group and in the easternmost interior region. It is proposed that Siberia was colonized by S. alpinus in two stages: from the west by the Eurasian group and later from the east by the Bering group. The high diversity of Eurasian group haplotypes in Siberia indicates its earlier colonization by S. alpinus as compared with the European Alps. This colonization was rapid, proceeded from a diverse gene pool, and was followed by differential survival of ancestral mtDNA lineages in different basins and regions, and local mutational events in isolated populations. The results presented here support a northern origin of Transbaikalian S. alpinus , the dispersion of S. alpinus to the Lake Baikal Basin from the Lena Basin, segregation of S. alpinus between Lena tributaries and their restricted migration over the divides between sub‐basins. These results also support sympatric origin of intralacustrine forms of S. alpinus .

Tropical nematode diversity: vertical stratification of nematode communities in a Costa Rican humid lowland rainforest - T. O. POWERS; D. A. NEHER; P. MULLIN; A. ESQUIVEL; R. M. GIBLIN‐DAVIS; N. KANZAKI; S. P. STOCK; M. M. MORA; L. URIBE‐LORIO (Molecular Ecology, 2009)
Comparisons of nematode communities among ecosystems have indicated that, unlike many organisms, nematode communities have less diversity in the tropics than in temperate ecosystems. There are, however, few studies of tropical nematode diversity on which to base conclusions of global patterns of diversity. This study reports an attempt to estimate nematode diversity in the lowland tropical rainforest of La Selva Biological Research Station in Costa Rica. We suggest one reason that previous estimates of tropical nematode diversity were low is because habitats above the mineral soil are seldom sampled. As much as 62% of the overall genetic diversity, measured by an 18S ribosomal barcode, existed in litter and understorey habitats and not in soil. A maximum‐likelihood tree of barcodes from 360 individual nematodes indicated most major terrestrial nematode lineages were represented in the samples. Estimated ‘species’ richness ranged from 464 to 502 within the four 40 × 40 m plots. Directed sampling of insects and their associated nematodes produced a second set of barcodes that were not recovered by habitat sampling, yet may constitute a major class of tropical nematode diversity. While the generation of novel nematode barcodes proved relatively easy, their identity remains obscure due to deficiencies in existing taxonomic databases. Specimens of Criconematina, a monophyletic group of soil‐dwelling plant‐parasitic nematodes were examined in detail to assess the steps necessary for associating barcodes with nominal species. Our results highlight the difficulties associated with studying poorly understood organisms in an understudied ecosystem using a destructive (i.e. barcode) sampling method.

Preliminary investigations of the colonisation of upper respiratory tract tissues of infants using a paediatric formulation of the oral probiotic Streptococcus salivarius K12 - D. A. Power; J. P. Burton; C. N. Chilcott; P. J. Dawes; J. R. Tagg (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Stoichiometry of soil enzyme activity at global scale - Robert L. Sinsabaugh; Christian L. Lauber; Michael N. Weintraub; Bony Ahmed; Steven D. Allison; Chelsea Crenshaw; Alexandra R. Contosta; Daniela Cusack; Serita Frey; Marcy E. Gallo; Tracy B. Gartner; Sarah E. Hobbie; et al. (Ecology Letters, 2008)
Extracellular enzymes are the proximate agents of organic matter decomposition and measures of these activities can be used as indicators of microbial nutrient demand. We conducted a global‐scale meta‐analysis of the seven‐most widely measured soil enzyme activities, using data from 40 ecosystems. The activities of β‐1,4‐glucosidase, cellobiohydrolase, β‐1,4‐ N ‐acetylglucosaminidase and phosphatase g −1 soil increased with organic matter concentration; leucine aminopeptidase, phenol oxidase and peroxidase activities showed no relationship. All activities were significantly related to soil pH. Specific activities, i.e. activity g −1 soil organic matter, also varied in relation to soil pH for all enzymes. Relationships with mean annual temperature (MAT) and precipitation (MAP) were generally weak. For hydrolases, ratios of specific C, N and P acquisition activities converged on 1 : 1 : 1 but across ecosystems, the ratio of C : P acquisition was inversely related to MAP and MAT while the ratio of C : N acquisition increased with MAP. Oxidative activities were more variable than hydrolytic activities and increased with soil pH. Our analyses indicate that the enzymatic potential for hydrolyzing the labile components of soil organic matter is tied to substrate availability, soil pH and the stoichiometry of microbial nutrient demand. The enzymatic potential for oxidizing the recalcitrant fractions of soil organic material, which is a proximate control on soil organic matter accumulation, is most strongly related to soil pH. These trends provide insight into the biogeochemical processes that create global patterns in ecological stoichiometry and organic matter storage.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Over-expression of a gibberellin 2-oxidase gene from Phaseolus coccineus L. enhances gibberellin inactivation and induces dwarfism in Solanum species - C. Dijkstra; E. Adams; A. Bhattacharya; A. F. Page; P. Anthony; S. Kourmpetli; J. B. Power; K. C. Lowe; S. G. Thomas; P. Hedden; A. L. Phillips; M. R. Davey (Plant Cell Reports, 2008)

Phylogenetic analysis of Rhizoctonia solani subgroups associated with web blight symptoms on common bean based on ITS-5.8S rDNA - G. Godoy-Lutz; S. Kuninaga; J. R. Steadman; K. Powers (Journal of General Plant Pathology, 2008)

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

Analysis of clonal germplasm from five Saccharum species: S. barberi, S. robustum, S. officinarum, S. sinense and S. spontaneum. A study of inter- and intra species relationships using microsatellite markers - J. Steven Brown; R. J. Schnell; E. J. Power; Stephanie L. Douglas; David N. Kuhn (Genetic Resources and Crop Evolution, 2007)

An assessment of de‐calcification procedures for δ 13 C and δ 15 N analysis of yellow perch, walleye and Atlantic salmon scales - R. N. Sinnatamby; J. E. Bowman; J. B. Dempson; M. Power (Journal of Fish Biology, 2007)
The scales of three species of fishes, yellow perch Perca flavescens , walleye Sander vitreus and Atlantic salmon Salmo salar , were acidified and the isotopic signatures were compared to non‐acidified scales from the same fishes. No significant acidification effects on either carbon or nitrogen isotope signatures were found. Results contrast with earlier literature findings noting significant acidification effects and suggest acidification tests be undertaken before scales are used for temporal reconstruction of fish food web positions.

Denaturation of an extremely stable hyperthermophilic protein occurs via a dimeric intermediate - Sara Lawrence Powers; Clifford R. Robinson; Anne Skaja Robinson (Extremophiles, 2007)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

Ecosystem recovery: heathland response to a reduction in nitrogen deposition - SALLY A. POWER; EMMA R. GREEN; CHRIS G. BARKER; J. NIGEL B. BELL; MIKE R. ASHMORE (Global Change Biology, 2006)
Atmospheric deposition of nitrogen is responsible for widespread changes in the structure and function of sensitive seminatural ecosystems. The proposed reduction in emissions of nitrogenous pollutants in Europe under the Gothenburg Protocol raises the question of whether affected ecosystems have the potential to recover to their previous condition and, if so, over what timescale. Since 1998, we have monitored the response of a lowland heathland in southern England following the cessation of a long‐term nitrogen addition experiment, and subsequent management, assessing changes in vegetation growth and chemistry, soil chemistry and the soil microbial community. Persistent effects of earlier nutrient loading on Calluna growth and phenology, and on the abundance of lichens, were apparent up to 8 years after nitrogen additions ceased, indicating the potential for long‐term effects of modest nutrient loading (up to 15.4 kg N ha −1 yr −1 , over 7 years) on heathland ecosystems. The size and activity of the soil microbial community was elevated in former N‐treated plots, 6–8 years after additions ceased, suggesting a prolonged effect on the rate of nutrient cycling. Although habitat management in 1998 reduced nitrogen stores in plant biomass, effects on belowground nitrogen stores were small. Although some parameters (e.g. soil pH) recover pretreatment levels relatively rapidly, others (e.g. vegetation cover and microbial activity) respond much more slowly, indicating that the ecological effects of even small increases in nitrogen deposition will persist for many years after deposition inputs are reduced. Indeed, calculations suggest that the additional soil nitrogen storage associated with 7 years of experimental nitrogen inputs could sustain the observed effects on plant growth and phenology for several decades. Carry over effects on plant phenology and sensitivity to drought suggest that the persistence of vegetation responses to nitrogen deposition should be integrated into long‐term assessments of the impact of global climate change on sensitive ecosystems.

Comparative field performance over 3 years and two sites of transgenic wheat lines expressing HMW subunit transgenes - Peter R. Shewry; Stephen Powers; J. Michael Field; Roger J. Fido; Huw D. Jones; Gillian M. Arnold; Jevon West; Paul A. Lazzeri; Pilar Barcelo; Francisco Barro; Arthur S. Tatham; Frank Bekes; et al. (Theoretical and Applied Genetics, 2006)

2004 SIVB Congress Symposium Proceedings “Thinking Outside the Cell”: Plant Protoplast Technology: Status and Applications - Michael R. Davey; Paul Anthony; J. Brian Power; Kenneth C. Lowe (In Vitro Cellular & Developmental Biology - Plant, 2005)

Environmental Consequences of Intensively Managed Forest Plantations in the Pacific Northwest - John P. Hayes; Stephen H. Schoenholtz; Mitschka J. Hartley; Glen Murphy; Robert F. Powers; Dean Berg; Steven R. Radosevich (Journal of Forestry, 2005)
Environmental consequences of intensively managed forest plantations (IMFP) are manifested primarily through influences on biodiversity, soils, and water resources. These consequences may be positive, neutral, or negative, depending on the spatial and temporal context and site-specificdetails. Many aspects of environmental consequences of IMFPs are increasingly understood, but significant gaps in our knowledge remain. Societal environmental goals and objectives of IMFPs remain poorly articulated and fuel a lively, often heated, social dialogue that will likely continuefor some time to come.

Plant protoplast technology: Current status - Michael R. Davey; Paul Anthony; J. Brian Power; Kenneth C. Lowe (Acta Physiologiae Plantarum, 2005)

Transformed Roots of Lupinus mutabilis: Induction, Culture and Isoflavone Biosynthesis - Mehmet Babaoglu; Michael R. Davey; J. Brian Power; Frank Sporer; Michael Wink (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Novel approaches for regulating gas supply to plant systems in vitro: Application and benefits of artificial gas carriers - Kenneth C. Lowe; Paul Anthony; J. Brian Power; Michael R. Davey (In Vitro Cellular & Developmental Biology - Plant, 2003)

Plant regeneration by somatic embryogenesis and organogenesis in commercial pineapple (Ananas comosus L.) - Suneerat Sripaoraya; Robert Marchant; J. Brian Power; Michael R. Davey (In Vitro Cellular & Developmental Biology - Plant, 2003)

Shifting Priorities at the Department of Energy's Bomb Factories: Protecting Human and Ecological Health - JOANNA BURGER; THOMAS M. LESCHINE; MICHAEL GREENBERG; JAMES R. KARR; MICHAEL GOCHFELD; CHARLES W. POWERS (Environmental Management, 2003)

Growth and Dietary Niche in Salvelinus Alpinus and Salvelinus Fontinalis as Revealed by Stable Isotope Analysis - Michael Power; Geoffrey Power; Francçois Caron; Richard R. Doucett; Karin R.A. Guiguer (Environmental Biology of Fishes, 2002)

N uptake and N status in ponderosa pine as affected by soil compaction and forest floor removal - Armando G. Gomez; Robert F. Powers; Michael J. Singer; William R. Horwath (Plant and Soil, 2002)

Using stable isotopes to confirm the trophic ecology of Arctic charr morphotypes from Lake Hazen, Nunavut, Canada - K. R. R. A. Guiguer; J. D. Reist; M. Power; J. A. Babaluk (Journal of Fish Biology, 2002)
Stable isotopes of carbon and nitrogen were used to examine differences in the feeding ecology of sympatric morphotypes of Arctic charr Sahelinus alpinus from Lake Hazen, Ellesmere Island, in the Canadian High Arctic. Large and small morphotypes possessed significantly different carbon and nitrogen signatures with large‐form Arctic charr being more depleted in 13 C and more enriched in 15 N than the small‐form. Isotope and stomach content analyses yielded consistent results and indicated short‐ and long‐term reliance on fish as a food for large Arctic charr. Large‐form individuals predate on juveniles but do not predate on small‐form individuals ≥ 250 mm. The observed cannibalism by large‐form individuals, therefore, does not act to maintain the bimodal length‐frequency distribution in Lake Hazen. Bimodality is argued to arise for ecological reasons connected with differing habitat use by the morphotypes and the associated differences in resource consumption opportunities.

Contributions of forage competition, harvest, and climate fluctuation to changes in population growth of northern white-tailed deer - Brent R. Patterson; Vince A. Power (Oecologia, 2002)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

Neurovirulence depends on virus input titer in brain in feline immunodeficiency virus infection: Evidence for activation of innate immunity and neuronal injury - J. B. Johnston; C Silva; T Hiebert; R Buist; M. R. Dawood; J Peeling; C Power (Journal of NeuroVirology, 2002)

Molecular systematics of Solanum section Lycopersicum (Lycopersicon) using the nuclear ITS rDNA region - J. A. Marshall; S. Knapp; M. R. Davey; J. B. Power; E. C. Cocking; M. D. Bennett; A. V. Cox (Theoretical and Applied Genetics, 2001)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

Winter movements and habitat use of riverine brown trout, white sucker and common carp in relation to flooding and ice break‐up - R. S. Brown; G. Power; S. Beltaoa (Journal of Fish Biology, 2001)
Movement of radio‐tagged riverine brown trout Salmo trutta , white sucker Catostomus commersoni and common carp Cyprinus carpio in the Grand River, Ontario, was minimal during the winter except during periods of high water discharge or the break‐up of river ice. Ice break‐up and flooding occur when southern air masses penetrate northwards in winter and as air temperatures increase in spring. Both white suckers and common carp moved the longest distances, generally in a downstream direction, during flooding and ice break‐up. Brown trout moved less during these times. All three species had positive relationships between distance moved and water discharge. During periods of high water discharge and ice break‐up, white suckers and common carp used backwater habitats more and main channel habitats less than during periods of low water discharge. During high flows, brown trout tended to use runs more and pools less. The break‐up of river ice and accompanying flooding resulted in several fish being stranded on the floodplain. Backwater habitats appear to be important areas of refuge for riverine fishes during periods of flooding and ice break‐up.

A simple and rapid procedure to establish embryogenic cell suspensions as a source of protoplasts for efficient plant regeneration from two Chinese commercial rice cultivars - K. Tang; X. Sun; D. An; J. B. Power; E. C. Cocking; M. R. Davey (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Genetic transformation of wheat: progress during the 1990s into the Millennium - Heidi M. Ingram; Nancy L. Livesey; J. Brian Power; Michael R. Davey (Acta Physiologiae Plantarum, 2001)

Comparison of sensory differences of stored Russet Burbank potatoes treated with CIPC and alternative sprout inhibitors - Terri D. Boylston; Joseph R. Powers; Karen M. Weiler; Jian Yang (American Journal of Potato Research, 2001)

Stratigraphical distribution of platinum-group minerals in the Eastern Layered Series, Rum, Scotland - M. R. Power; D. Pirrie; J. C. Ø. Andersen; A. R. Butcher (Mineralium Deposita, 2000)

Effects of hanging ice dams on winter movements and swimming activity of fish - R. S. Brown; G. Power; S. Beltaos; T. A. Beddow (Journal of Fish Biology, 2000)
Formation of a hanging dam, a large, thick sub‐surface accumulation of frazil ice that blocked river flow, altered physical environmental conditions dramatically and common carp Cyprinus carpio , and brown trout Salmo trutta , evacuated the pool in which the dam developed. A mean of 80·1% of the pool volume was filled with frazil ice. Mean and bottom water velocities in the pool increased from 6 to 27 cm s −1 and from 4 to 21 cm s −1 , respectively, when the hanging dam formed, and water depth decreased from a mean of 2·25 to 0·45 m. Activity levels of fish leaving the pool varied. Two carp had higher swimming activities when in the over wintering pool, compared to the period when they were out of it, and a third showed opposite results.

The seasonal cycle in coupled ocean-atmosphere general circulation models - C. Covey; A. Abe-Ouchi; G. J. Boer; B. A. Boville; U. Cubasch; L. Fairhead; G. M. Flato; H. Gordon; E. Guilyardi; X. Jiang; T. C. Johns; H. Le Treut; et al. (Climate Dynamics, 2000)

Plant regeneration from embryogenic cultures of Phragmites australis (Cav.) Trin. Ex Steud. - Csaba Máthé; Márta M. Hamvas; István Grigorszky; Gábor Vasas; Erika Molnár; J. Brian Power; Michael R. Davey; George Borbély (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Combined PI–DAPI staining (CPD) reveals NOR asymmetry and facilitates karyotyping of plant chromosomes - S. C. Andras; T. P. V. Hartman; J. Alexander; R. McBride; J. A. Marshall; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 2000)

Agrobacterium-mediated transformation of Lupinus mutabilis L. using shoot apical explants - Mehmet Babaoglu; Matthew S. McCabe; J. Brian Power; Michael R. Davey (Acta Physiologiae Plantarum, 2000)

Temporal abundance patterns and growth of juvenile herring and sprat from the Thames estuary 1977–1992 - M. Power; M. J. Attrill; R. M. Thomas (Journal of Fish Biology, 2000)
Most herring Clupea harengus and sprat Sprattus sprattus sampled from West Thurrock power station intake screens, middle Thames estuary, between 1977 and 1992 were age‐0 and followed regular patterns of seasonal occurrence. Juvenile herring entered the estuary in July, peaked in abundance November to March, and then declined. Juvenile sprat first appeared in September and peaked in abundance in January. Neither species was abundant in summer samples. While in the estuary, herring and sprat increased in length an average of 4·0 and 0·33 cm respectively. Abundance of both species was significantly affected by temperature, temporal trend, shoaling behaviour and seasonal variables, and of herring by suspended solids. Interactions between environmental variates did not influence the abundance of either species. As estuarine clupeids were influenced by a complex set of events within and outside the estuary, estuarine monitoring studies alone will not be sufficient for understanding the changes in estuarine fish communities resulting from future human activity.

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

The effect of food deprivation and refeeding on the liver, thyroid hormones and transthyretin in sea bream - D. M. Power; J. Melo; C. R. A. Santos (Journal of Fish Biology, 2000)
There was a significant reduction in body weight of sea bream Sparus aurata and the hepatosomatic index after 3 weeks food deprivation. Liver biochemical indices and morphology were altered by food deprivation, there was a loss of eosin staining in hepatocyte cytoplasm and the appearance of large depleted vacuoles. Cell and nuclear area were significantly reduced ( P T 3 (33·98±12·47 ng ml ‐1 ) and T 4 (16·54±9·5 ng ml ‐1 ) was significantly ( P 0·001) lower than the control (66·52±13·4 and 56·83±7·3, respectively). Refeeding for 1 week restored circulating T 3 ( P 0·05) close to control levels but did not significantly affect the concentration of T 4 . Northern blotting with an homologous probe for transthyretin (TTR) demonstrated clearly the expression of a single mRNA transcript of 0·7 kb for this protein in the liver. The level of TTR message was substantially reduced below control levels in the liver of fasted fish and 1 week refeeding failed to restore expression.

A Drop-spreading Technique to Produce Cytoplasm-free Mitotic Preparations from Plants with Small Chromosomes - S. C. Andras; T. P. V. Hartman; J. A. Marshall; R. Marchant; J. B. Power; E. C. Cocking; M. R. Davey (Chromosome Research, 1999)

Effect of Single and Paired Metal Inputs in Soil on a Stress-Inducible Transgenic Nematode - R. S. Power; D. I. de Pomerai (Archives of Environmental Contamination and Toxicology, 1999)

Expression of a chimeric nitrate reductase gene in transgenic lettuce reduces nitrate in leaves - I. S. Curtis; J. B. Power; A. M. M. de Laat; M. Caboche; M. R. Davey (Plant Cell Reports, 1999)

Increased stable inheritance of herbicide resistance in transgenic lettuce carrying a petE promoter-bar gene compared with a CaMV 35S-bar gene - M. S. McCabe; F. Schepers; A. van der Arend; U. Mohapatra; A. M. M. de Laat; J. B. Power; M. R. Davey (Theoretical and Applied Genetics, 1999)

Intergeneric somatic hybrids of rice [Oryza sativa L. (+) Porteresia coarctata (Roxb.) Tateoka] - N. B. Jelodar; N. W. Blackhall; T. P. V. Hartman; D. S. Brar; G. Khush; M. R. Davey; E. C. Cocking; J. B. Power (Theoretical and Applied Genetics, 1999)

Evidence for anadromy in a southern relict population of Arctic charr from North America - R. R. Doucett; M. Power; G. Power; F. Caron; J. D. Reist (Journal of Fish Biology, 1999)
Stable isotope analysis of Arctic charr from a southern relict population in Québec showed that some individuals adopted anadromy as a life‐history strategy, but the strategy did not predominate in the population. Differences in length‐at‐age, ages and sex ratios between identified freshwater residents and anadromous individuals were consistent with previous descriptions of partially migratory populations. This suggests that anadromy in relict populations in Québec is associated with niche shift and occurs as a conditional response to opportunities for maximizing the rewards (e.g. fitness) of habitat use.

A stable transformation system for the ornamental plant, Datura meteloides D. C. - I. S. Curtis; J. B. Power; P. Hedden; D. A. Ward; A. Phillips; K. C. Lowe; M. R. Davey (Plant Cell Reports, 1999)

Use of the Polymerase Chain Reaction for Rapid Detection of High-Level Mupirocin Resistance in Staphylococci - R. M. Anthony; A. M. Connor; E. G. M. Power; G. L. French (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Expression of the Bar Gene Confers Herbicide Resistance in Transgenic Lettuce - Umaballava Mohapatra; Matthew S. McCabe; J. Brian Power; Frank Schepers; Aad Van Der Arend; Michael R. Davey (Transgenic Research, 1999)

Stress-inducible transgenic nematodes as biomonitors of soil and water pollution - R S Power; H E David; M H A Z Mutwakil; K Fletcher; C Daniells; M A Nowell; J L Dennis; A Martinelli; R Wiseman; E Wharf; D I de Pomerai (Journal of Biosciences, 1998)

Efficient in vitro shoot regeneration responses of Phaseolus vulgaris and P. coccineus - Marta Santalla; J. Brian Power; Michael R. Davey (Euphytica, 1998)

A comparison of methods for direct gene transfer into maize (Zea mays L.) - E. M. Southgate; M. R. Davey; J. B. Power; R. J. Westcott (In Vitro Cellular & Developmental Biology - Plant, 1998)

DNA Isolation and AFLP™ Genetic Fingerprinting of shape Theobroma cacao (L.) - Matthew D. Perry; Michael R. Davey; J. Brian Power; Kenneth C. Lowe; H. Frances J. Bligh; Paul S. Roach; Chris Jones (Plant Molecular Biology Reporter, 1998)

Shoot regeneration from cultured root explants of spinach (Spinacia oleracea L.): a system for Agrobacterium transformation - K. A. Knoll; K. C. Short; I. S. Curtis; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

Somatic embryogenesis and plant regeneration from stem explants of Moricandia arvensis - W. Craig; A. Wiegand; C. M. O'Neill; R. J. Mathias; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

Carbon dioxide-gassed fluorocarbon enhances micropropagation of rose (Rosa chinesis Jacq.) - J. Wardrop; K. C. Lowe; M. R. Davey; R. Marchant; J. B. Power (Plant Cell Reports, 1997)

Strategies for promoting division of cultured plant protoplasts: synergistic beneficial effects of haemoglobin (Erythrogen) and Pluronic F-68 - P. Anthony; K. C. Lowe; M. R. Davey; J. B. Power (Plant Cell Reports, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Non-linear climate feedback analysis in an atmospheric general circulation model - R. A. Colman; S. B. Power; B. J. McAvaney (Climate Dynamics, 1997)

Isolation and culture of mesophyll protoplasts from Rosa hybrida - R. Marchant; M.R. Davey; J.B. Power (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)

Homoeologous pairing and recombination in backcross derivatives of tomato somatic hybrids [Lycopersicon esculentum (+) L. peruvianum] - A. S. Parokonny; J. A. Marshall; M. D. Bennett; E. C. Cocking; M. R. Davey; J. Brian Power (Theoretical and Applied Genetics, 1997)

Characterisation of an avian influenza virus nucleoprotein expressed inE. coli and in insect cells - V. R. Harley; K. A. Mather; B. E. Power; J. L. McKimm-Breschkin; P. J. Hudson (Archives of Virology, 1990)

Biochemical genetics of Fundulus heteroclitus (L.). I. Temporal and spatial variation in gene frequencies of Ldh-B, Mdh-A, Gpi-B, and Pgm-A - Dennis A. Powers; Allen R. Place (Biochemical Genetics, 1978)

Genetic bases for protein polymorphism in Fundulus heteroclitus (L.). I. Lactate dehydrogenase (Ldh-B), malate dehydrogenase (Mdh-A), glucosephosphate isomerase (Gpi-B), and phosphoglucomutase (Pgm-A) - Allen R. Place; Dennis A. Powers (Biochemical Genetics, 1978)

Spectral analysis of the high-frequency electrocardiogram in contusive myocardial injury - T. D. Schick; S. R. Powers (Annals of Biomedical Engineering, 1978)